Organic el display device

JP2025035142APending Publication Date: 2025-03-13TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023141988
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-13

Smart Images

  • Figure 2025035142000001_ABST
    Figure 2025035142000001_ABST
Patent Text Reader

Abstract

To provide an organic EL display device with high bending reliability, which inhibits peeling by embedding a reverse taper-shaped spacer in a pixel division layer.SOLUTION: An organic EL display device comprises a substrate, an organic EL layer and a second electrode. The substrate has a base material, on which a first electrode, a pixel division layer and a reverse taper-shaped spacer are formed. The reverse taper-shaped spacer is partially embedded in the pixel division layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic EL display device having a plurality of display pixels. [Background technology]

[0002] Organic electroluminescence (EL) display devices have been attracting attention as the next generation of flat panel displays. OLED is a phenomenon in which electroluminescence occurs when electricity is passed through an organic EL layer made of organic compounds placed between two electrodes. OLED display devices are display devices that use light-emitting elements using OLED as display pixels. OLED display devices are self-luminous, so they are capable of displaying images with a wide viewing angle, high-speed response, and high contrast. Furthermore, by using substrates such as thin glass or plastic resin, they can be made lighter, thinner, and more flexible, and research and development into them has been actively conducted in recent years.

[0003] This organic EL display device is composed of many thin film layers, such as a substrate, a light-emitting layer, and a sealing layer. Therefore, when using an organic EL display device, a high peeling prevention effect (reliability) against peeling of these layers is required. In particular, in areas with low adhesion, technologies have been proposed to prevent peeling by using features related to the surface shape, such as unevenness and taper angle, and chemical bonds through material selection (e.g., Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-74238 A [Patent Document 2] International Publication No. 2015 / 046296 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the effect of preventing peeling due to bending stress was insufficient only by using unevenness and taper angles. Furthermore, the technology using chemical bonding with photosensitive resin had a problem of low productivity in terms of process management and reproducibility. Therefore, the object of the present invention is to provide an organic EL display device that is unlikely to peel off and has high bending reliability. [Means for solving the problem]

[0006] In order to solve the above problems, the organic EL display device of the present invention has the following configuration. (1) An organic EL display device having a substrate, an organic EL layer, and a second electrode, the substrate having a first electrode, a pixel division layer, and a spacer having an inverted tapered shape on a base material, and a portion of the spacer having an inverted tapered shape is embedded in the pixel division layer. (2) The organic electroluminescence display device according to (1), wherein T1, T2 and T3 satisfy the following condition 1, where T1 (μm) is the thickness of the inverted tapered spacer, T2 (μm) is the embedding depth of a portion of the inverted tapered spacer embedded in the pixel division layer, and T3 (μm) is the thickness of the pixel division layer.

[0007] Condition 1: T3≧T2≧T1×0.2 (3) The organic electroluminescence display device according to (2), in which T1, T2 and T3 satisfy the following condition 2:

[0008] Condition 2: T3 = T2 ≧ T1 × 0.2 (4) The organic electroluminescence display device according to any one of (1) to (3), wherein the spacer having an inverse tapered shape contains a coloring material. (5) The organic electroluminescence display device according to any one of (1) to (4), wherein the organic electroluminescence layer contains a hole-transporting polymer compound. (6) The organic EL display device according to any one of (1) to (5), wherein the organic EL layer contains a compound having a phenanthroline skeleton. (7) The organic electroluminescence display device according to any one of (1) to (6), wherein the organic electroluminescence layer contains a compound having a terpyridine skeleton. Effect of the Invention

[0009] According to the present invention, it is possible to provide an organic EL display device which is less susceptible to peeling and has high folding reliability. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an organic EL display device of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing an example of a substrate in the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing a spacer having an inverse tapered shape. [Figure 4] FIG. 4 is a schematic diagram showing the embedding depth of a spacer. [Diagram 5] FIG. 11 is a schematic cross-sectional view showing an example of a substrate in which T2 is the same as T3. [Figure 6] 1 is a schematic diagram showing an example of a spacer-embedded portion having a reverse tapered shape; FIG. [Figure 7] 1 is a schematic diagram showing an example of a spacer-embedded portion having a forward tapered shape; FIG. [Figure 8] 1 is a schematic diagram showing an example of a spacer-embedded portion having a reverse tapered shape; FIG. [Figure 9] 1 is a schematic cross-sectional view of a top-emission type organic EL display device that is an example of the present invention. [Figure 10] FIG. 2 is a schematic diagram of a substrate used in an embodiment of the present invention. [Figure 11] FIG. 2 is a schematic diagram of a first electrode, a pixel dividing layer, and a spacer in an embodiment of the present invention. [Figure 12] FIG. 2 is a schematic diagram illustrating a structure of a spacer. [Figure 13] FIG. 2 is a schematic diagram showing a bending reliability test in an example of the present invention. [Figure 14] FIG. 1 is a schematic diagram of an organic EL display device produced in an example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, a mode for carrying out the present invention (hereinafter, referred to as "embodiment") will be described in detail. Note that the present invention should not be limited to only the embodiment described below.

[0012] <Organic EL display device> The organic EL display device of the present invention is an organic EL display device having a plurality of display pixels. It is roughly classified into a top emission type and a bottom emission type according to the direction of extracting light emitted from the organic EL layer, but is not particularly limited thereto. It is also roughly classified into a passive driving type that selects electrodes divided into rows and columns, and an active driving type that has a driving circuit for each display pixel, but is not particularly limited thereto according to the driving method.

[0013] The organic EL display device of the present invention is an organic EL display device having a substrate, an organic EL layer, and a second electrode, the substrate having a first electrode, a pixel dividing layer, and a spacer having an inverted tapered shape on a base material, and a portion of the spacer having an inverted tapered shape is embedded in the pixel dividing layer.

[0014] FIG. 1 shows a schematic cross-sectional view of an organic EL display device according to the present invention. The organic EL display device has a first electrode 2 on a substrate 1. A pixel division layer 3 is provided thereon, and an opening is provided in the pixel division layer 3 above the first electrode 2. The opening becomes a display pixel in the organic EL display device. Furthermore, in the organic EL display device of the present invention, a spacer 4 having an inverse tapered shape is provided so that a part of the spacer 4 is embedded in the pixel division layer 3. In the organic EL display device, a unit having the first electrode 2, the pixel division layer 3, and the spacer 4 having an inverse tapered shape on the substrate 1 is referred to as a substrate. Furthermore, an organic EL layer 5 and a second electrode 6 are provided on the substrate to form an organic EL display device.

[0015] <Substrate> FIG. 2 shows a schematic cross-sectional view of a substrate in an example of an organic EL display device of the present invention. In the organic EL display device of the present invention, the substrate is constituted as a minimum by only a substrate 1, a first electrode 2, a pixel division layer 3, and a spacer 4 having an inverse tapered shape, which will be described later. If the substrate has such a constitution, the substrate may further have wiring and a TFT (thin film transistor) 7 as a driving circuit. In addition to the TFT, the substrate may have a camera, sensors for reading ID and fingerprints, illuminance, and the like, and a pattern antenna for communication and power supply. In the substrate having such various components, it is preferable to provide a planarization layer 8. By providing the planarization layer 8, unevenness of the wiring and the TFT can be covered before the first electrode 2 is formed, and the substrate 1 can be planarized. By planarizing the substrate 1, defects of the first electrode 2 and the pixel division layer 3 provided on the substrate 1 can be prevented, and a high-quality substrate can be obtained.

[0016] In the present invention, components present below the first electrode 2 (on the substrate 1 side), such as wiring, TFTs, sensors, pattern antennas, and a planarizing layer, may all be treated as part of the substrate 1. In this case, the actual portion of the substrate 1 excluding wiring, TFTs, etc., is referred to as the base 1a of the substrate.

[0017] <Base material> The substrate 1 in FIG. 1 and the base 1a of the substrate in FIG. 2 can be a metal plate, a glass plate, a resin film, or the like. Any suitable material can be selected for supporting the display device itself and for transporting the display device during the manufacturing process. The thickness of the substrate needs to be sufficient to maintain mechanical strength. In particular, when flexibility is required, a resin film is preferred.

[0018] Regarding the glass material, it is preferable that the amount of ions eluted from the glass is small. Therefore, non-alkali glass or SiO 2 For example, soda lime glass coated with a barrier coat such as SiO2 can be used.

[0019] The material of the resin film is preferably a resin selected from polybenzoxazole resin, polyamideimide resin, polyimide resin, polyamide resin, and poly(p-xylylene) resin, because of its excellent light transmittance. The substrate may contain one of these resins alone or in combination.

[0020] For example, when forming the substrate from a polyimide resin, the substrate can be formed by applying a solution containing a polyamic acid resin (including a partially imidized polyamic acid) which is a precursor of the polyimide resin, or a soluble polyimide resin, to a supporting substrate and baking the applied solution.

[0021] In addition, since the above-mentioned light-emitting element is known to be vulnerable to oxygen and moisture, a gas barrier layer may be provided as a component of the substrate. In particular, when the substrate is a resin film, a highly reliable display device can be obtained by laminating a thin inorganic film as a gas barrier layer. Furthermore, the substrate may be provided with wiring, TFT, a planarization layer, etc.

[0022] <First electrode> In the present invention, the first electrode 2 is preferably a light-transmitting electrode in the case of a bottom emission type, and a light-reflective electrode in the case of a top emission type.

[0023] When the first electrode 2 is of a bottom emission type, examples of materials that can be used include, but are not limited to, conductive metal oxides such as transparent tin oxide, indium oxide, and indium tin oxide (ITO), metals such as gold, silver, and chromium, inorganic conductive substances such as copper iodide and copper sulfide, and conductive polymers such as polythiophene, polypyrrole, and polyaniline.

[0024] When the first electrode 2 is a top emission type, a material and a film thickness that show high reflectance and low electrical resistance to visible light are preferable. Furthermore, the material is preferably selected from the viewpoints of wet etching and cleaning in the subsequent process, and weather resistance in the storage and use environment. In particular, Ag or an Ag alloy film mainly containing Ag is preferable as the material because it satisfies both reflectance and electrical resistance. Ag alloy films can be made of AgPdCu or AgTiCu, etc., whose main component is Ag. These Ag alloy films are preferably laminated with oxide conductive films such as ITO films and IZO (indium oxide zinc oxide) films, because low contact resistance with the organic EL layer can be realized. In addition, Al or an Al alloy film mainly containing Al is also good as a top emission type first electrode. An Al-Ni alloy film containing 0.1 to 2 atomic % of Ni is preferable because it has a high reflectance comparable to that of pure Al. In addition, reflective metal films such as a molybdenum (Mo) film and a tungsten (W) film can also be used.

[0025] The electrical resistance of the first electrode is not limited as long as it can supply a sufficient current for the light emission of the light emitting element, but it is preferable that the resistance is low from the viewpoint of the power consumption of the light emitting element. The film thickness is generally set to be between 100 nm and 300 nm in order to achieve both optical properties and electrical properties.

[0026] The first electrode can be formed by a known method, for example, by forming a film by a vacuum film forming method such as sputtering, and then patterning the film by etching using a photoresist.

[0027] <Pixel division layer> In the organic EL display device of the present invention, a pixel division layer 3 is formed on the substrate 1 and the first electrode 2. The pixel division layer is preferably insulating. The openings of this pixel division layer (sometimes referred to as pixel openings) function as display pixels of the organic EL display device, so the pixel division layer is patterned to have openings. In the patterning of the pixel openings on the first electrode, it is important to process the pixel openings without leaving any foreign matter or residues, since they may directly lead to defects in the display device, such as short circuits and black spots. In addition, the pixel division layer covers the edge of the first electrode, which also leads to suppressing short circuits and disconnection of the second electrode that occur at the edge of the first electrode, and thus improving the reliability of the display device. In addition, in order to prevent disconnection of the second electrode at the edge of the pixel opening, the edge of the pixel opening is preferably gently forward tapered.

[0028] The pixel division layer is not limited to either a known organic material or an inorganic material, but from the viewpoint of processability as described above, it is preferable that the pixel division layer includes a cured film of a photosensitive resin composition. The pixel division layer may be a single layer or a multilayer.

[0029] A known method can be used to form the pixel division layer. Among them, a wet coating method is preferred because a thin film can be uniformly formed on a large substrate. Examples of the wet coating method include spin coating, slit coating, dip coating, spray coating, and printing. The thickness of the pixel division layer is usually 0.3 μm to 10 μm, but is not particularly limited as long as it is sufficient to cover the unevenness of the first electrode.

[0030] <Spacer> The organic EL display device of the present invention has a spacer in contact with the pixel division layer. Generally, the spacer is provided as a contact point of the substrate in the manufacturing process or as a support like a pillar in the completed display device. Also, depending on the shape, the spacer can be provided for various purposes, such as suppressing leakage current between adjacent display pixels. However, in the present invention, the spacer is made in an inverted tapered shape, which has an anchor effect on the organic EL layer and the sealing layer, and can suppress peeling from the substrate. Furthermore, by embedding a part of the inverted tapered spacer in the pixel division layer, it is possible to suppress peeling of the spacer from the pixel division layer, and to produce a greater peeling suppression effect.

[0031] The material of the spacer is not limited to either a known organic or inorganic material, as in the pixel division layer, but is preferably a cured film of a photosensitive resin composition from the viewpoint of processability and shape. The thickness of the spacer is usually 0.5 μm to 10 μm, but is not particularly limited as long as it is sufficient to suppress peeling at the interface between the substrate and the organic EL layer.

[0032] <Reverse tapered spacer> In the organic EL display device of the present invention, the spacer needs to have an inverse tapered shape as a method for suppressing peeling between the substrate and the organic EL layer. A schematic diagram of an inverse tapered spacer is shown in FIG. 3. Here, the inverse tapered shape of the spacer refers to a state in which the angle formed by the exposed spacer side surface and the surface of the pixel division layer exceeds 90 degrees. Specifically, in FIG. 3, the angle B formed by the tangent at the position (point A) at 50% of the height of the exposed spacer 4 side surface and the surface of the pixel division layer 3 that is approximately parallel to the substrate (hereinafter, this angle may be referred to as the "taper angle of the spacer exposed portion") exceeds 90 degrees. Here, the spacer exposed portion refers to a portion of the spacer 4 that protrudes above the pixel division layer 3 when a part of the spacer 4 is embedded in the pixel division layer 3.

[0033] Although the anchor effect is increased by increasing the taper angle of the exposed spacer portion, if the taper angle is too large, the shape may become unstable or become the starting point of defects in the organic EL layer or the second electrode, which may cause a decrease in the reliability of the display device. In terms of the anchor effect and ease of processing the spacer, a taper angle of 91 to 120° is preferable.

[0034] <Spacer embedding depth and taper angle in pixel division layer> Embedding a part of the inverted tapered spacer in the pixel division layer is preferable because it can prevent the spacer from peeling off from the pixel division layer and improve bending reliability. Specifically, when the thickness of the inverted tapered spacer is T1 (μm), the embedding depth of the part of the inverted tapered spacer embedded in the pixel division layer is T2 (μm), and the thickness of the pixel division layer is T3 (μm), it is preferable that T1, T2, and T3 satisfy the following condition 1.

[0035] Condition 1: T3≧T2≧T1×0.2 Furthermore, it is more preferable that T1, T2 and T3 satisfy the following condition 2.

[0036] Condition 2: T3 = T2 ≧ T1 × 0.2 A schematic diagram showing the embedding depth of the spacer in the present invention is shown in Fig. 4. First, in order to prevent the spacer 4 from peeling off from the pixel division layer 3, it is preferable that the embedding depth T2 is at least a certain size. It is preferable that the size of T2 is at least 20% of T1, taking into account the balance of the laminated structure including the organic EL layer and the sealing layer. If T2 is less than 20% of T1, the spacer is likely to peel off from the pixel division layer.

[0037] Furthermore, due to the structure in which the spacers 4 are embedded in the pixel division layer 3, the thickness T3 of the pixel division layer is equal to or greater than T2. ​​Among these, the state in which T2 reaches its maximum value is when T2 is the same as T3, i.e., when the bottom end of the spacer 4 contacts the substrate 1. This is preferable because it makes it even more difficult for the spacer and the pixel division layer to peel off. A specific example of such a structure is shown in Figure 5. With this structure only, it is also possible to form the spacers 4 before forming the pixel division layer 3, which is also preferable because it increases the options for the manufacturing method of each layer.

[0038] In the organic EL display device of the present invention, the spacer embedded portion is preferably inverted tapered shape as a method for suppressing peeling between the pixel division layer and the spacer. Here, the spacer embedded portion refers to a portion of the spacer that is embedded inside the pixel division layer. A specific example is shown in FIG. 6. Here, the inverted tapered shape refers to a state in which the angle formed by the embedded spacer side surface and the pixel division layer surface exceeds 90 degrees. Specifically, in FIG. 6, the inverted tapered shape refers to a state in which the angle D formed by the tangent at a position (point C) at 50% of the embedded depth of the embedded spacer side surface and the surface approximately parallel to the substrate at the surface of the pixel division layer 3 exceeds 90 degrees (hereinafter, this angle may be referred to as the "taper angle of the spacer embedded portion").

[0039] Although the anchor effect is increased by increasing the taper angle of the spacer embedded portion, if the taper angle is too large, shape instability is likely to occur, which may become the starting point of defects in the pixel division layer and spacers, resulting in reduced reliability as a display device. In terms of the anchor effect and ease of processing the insulating layer, a taper angle of 91 to 120° is preferable.

[0040] However, the structure of the spacer is not particularly limited, and can be selected from various options depending on the processability of the pixel division layer and the spacer. An example is shown in Figures 7 and 8.

[0041] <Coloring materials> The material of the pixel division layer and the spacer is not limited to either organic or inorganic. In the present invention, it is preferable that the pixel division layer and the spacer contain a coloring material. By coloring the pixel division layer and the spacer, it is possible to block incident light from the outside. Furthermore, it is possible to obtain an effect of blocking the component of the light emitted from the organic EL layer that has propagated through the pixel division layer. This is preferable because it is possible to improve the display performance of the display device by suppressing the reflectance of the display device surface and suppressing color mixing for each pixel.

[0042] In particular, when the spacer includes a cured film of a photosensitive resin composition, the following coloring material is preferred. In the present invention, the coloring material refers to a compound that absorbs light of a specific wavelength, and in particular, a compound that absorbs light of a visible light wavelength (380 nm to 780 nm) to color the spacer. The content of the coloring material used in the present invention is preferably 1% by weight or more in the spacer, more preferably 10% by weight or more, and even more preferably 15% by weight or more. When the content ratio is within the above range, the light-shielding property, coloring property, or color-tuning property can be improved. On the other hand, the content ratio is preferably 70% by weight or less, more preferably 65% ​​by weight or less, and even more preferably 60% by weight or less. When the content ratio is within the above range, the sensitivity during exposure can be improved.

[0043] Examples of coloring materials include known compounds such as (D1) organic pigments, (D2) inorganic pigments, and (D3) dyes that absorb light of visible light wavelengths and color the material white, red, orange, yellow, green, blue, or purple. Two or more of these coloring materials may be used in combination, or two or more colors may be used in combination. Combining two or more coloring materials is preferable because the resulting spacer has the effects described below. Combining two or more coloring materials can improve color-tuning properties, which allows light transmitted through a cured film of a photosensitive resin composition or light reflected from a cured film of a photosensitive resin composition to be toned to a desired color coordinate.

[0044] By using the organic pigment (D1) as the coloring material (D), the organic pigment (D1) has a chemical structure change or functional group conversion function that is a characteristic of the organic pigment, and this function allows the transmission or absorption spectrum of the cured film of the photosensitive resin composition to be adjusted, for example, to transmit or block light of a desired specific wavelength, thereby improving the color toning properties.

[0045] Examples of the organic pigment (D1) include phthalocyanine pigments, anthraquinone pigments, quinacridone pigments, pyranthrone pigments, dioxazine pigments, thioindigo pigments, diketopyrrolopyrrole pigments, quinophthalone pigments, threne pigments, indoline pigments, isoindoline pigments, isoindolinone pigments, benzofuranone pigments, perylene pigments, aniline pigments, azo pigments, azomethine pigments, condensed azo pigments, carbon black, metal complex pigments, lake pigments, toner pigments, and fluorescent pigments. From the viewpoint of heat resistance, pigments selected from anthraquinone pigments, quinacridone pigments, pyranthrone pigments, diketopyrrolopyrrole pigments, benzofuranone pigments, perylene pigments, condensed azo pigments, and carbon black are preferred.

[0046] In the present invention, it is also preferable to further contain an organic black pigment and / or a mixed-color organic black pigment as the organic pigment (D1). Examples of the organic black pigment include benzodifuranone-based black pigments, perylene-based black pigments, and azomethine-based black pigments.

[0047] Benzodifuranone-based black pigments include, for example, pigments disclosed in International Publication No. 2009 / 010521. As commercially available benzodifuranone-based black pigments, "Irgaphor" (registered trademark) Black S0100CF and Experimental Black 582 (both manufactured by BASF) can be preferably used.

[0048] Examples of perylene-based black pigments include CI Pigment Black 31, CI Pigment Black 32, perylenetetracarboxylic acid benzimidazole or its derivatives, and the pigments disclosed in International Publication No. 2005 / 078023. Commercially available products include "Spectrasense" (registered trademark) Black S0084, L0086, K0087, and K0088 (all manufactured by BASF).

[0049] Examples of azomethine black pigments include those disclosed in U.S. Patent Application Publication No. 2002-121228. As a commercially available product, Chromofine Black A1103 (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.) can be used.

[0050] The mixed color organic black pigment refers to a pigment mixture containing at least one organic pigment (b-1) selected from organic yellow pigments, organic red pigments, and organic orange pigments, and at least one organic pigment (b-2) selected from organic blue pigments and organic purple pigments, in which the content of (b-2) is 20% by weight or more relative to the total amount of (b-1) and (b-2).

[0051] Examples of organic yellow pigments include CI Pigment Yellow 24, 120, 138, 139, 151, 175, 180, 185, 181, 192, 193, and 194. Examples of organic red pigments include CI Pigment Red 122, 123, 149, 178, 177, 179, 180, 189, 190, 202, 209, 254, 255, and 264. Examples of organic orange pigments include CI Pigment Orange 13, 36, 43, 60, 61, 62, 64, 71, and 72.

[0052] Examples of organic blue pigments include CI Pigment Blue 15, 15:1, 15:2, 15:3, 15:6, 16, 25, 56, 57, 60, 61, 64, 65, 66, 75, 79, 80. Examples of organic purple pigments include CI Pigment Violet 19, 23, 29, 32, 37.

[0053] By using the inorganic pigment (D2) as the coloring material (D), the heat resistance and weather resistance of the cured film of the photosensitive resin composition can be improved due to the excellent heat resistance and weather resistance that are characteristic of the inorganic pigment (D2). Examples of the inorganic pigment (D2) include zirconium nitride, zirconium oxide, titanium oxide, barium carbonate, zinc oxide, zinc sulfide, white lead, calcium carbonate, barium sulfate, white carbon, alumina white, silicon dioxide, kaolin clay, talc, bentonite, red iron oxide, molybdenum red, molybdenum orange, chrome vermilion, yellow lead, cadmium yellow, yellow iron oxide, titanium yellow, chromium oxide, viridian, titanium cobalt green, cobalt green, cobalt chrome green, Victoria green, ultramarine, Prussian blue, cobalt blue, cerulean blue, cobalt silica blue, cobalt zinc silica blue, manganese violet, cobalt violet, graphite, and silver-tin alloys; and fine particles, oxides, composite oxides, sulfides, sulfates, nitrates, carbonates, nitrides, carbides, and oxynitrides of metals such as titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, and silver.

[0054] (D3) Dyes are compounds that color an object by chemically adsorbing or strongly interacting with the surface structure of the object through the ionic or hydroxyl groups of the dye, and are generally soluble in solvents. In addition, dyes have high coloring power and high coloring efficiency because each molecule is adsorbed to the object. Dyes can be classified into, for example, direct dyes, reactive dyes, sulfur dyes, vat dyes, sulfur dyes, acid dyes, metal-containing dyes, metal-containing acid dyes, basic dyes, mordant dyes, acid mordant dyes, disperse dyes, cationic dyes, and fluorescent whitening dyes. In terms of materials, examples of the dyes include anthraquinone dyes, azo dyes, azine dyes, phthalocyanine dyes, methine dyes, oxazine dyes, quinoline dyes, indigo dyes, indigoid dyes, carbonium dyes, threne dyes, perinone dyes, perylene dyes, triarylmethane dyes, and xanthene dyes. From the viewpoints of solubility in organic solvents and heat resistance, preferred are dyes selected from the group consisting of anthraquinone dyes, azo dyes, azine dyes, methine dyes, triarylmethane dyes, and xanthene dyes.

[0055] <Organic EL layer> In the organic EL display device of the present invention, the configuration of the organic EL layer 5 is not particularly limited, and may be, for example, any of (1) hole transport layer / light emitting layer, (2) hole transport layer / light emitting layer / electron transport layer, and (3) light emitting layer / electron transport layer. Furthermore, the above configurations may be stacked in a tandem type with a charge generating layer interposed therebetween. The charge generating layer is also called an electron extracting layer, a connecting layer, an intermediate layer, an intermediate electrode, an intermediate conductive layer, and an intermediate insulating layer, and may be made of a known material configuration. By forming the organic EL layer into a tandem type, it is possible to expect improvements in luminance and emission life, and this is preferable. Specific examples of the tandem type include stacked structures such as (4) hole transport layer / light-emitting layer / electron transport layer / charge generation layer / hole transport layer / light-emitting layer / electron transport layer, (5) hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer / charge generation layer / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer, and (6) hole transport layer / light-emitting layer / electron transport layer / charge generation layer / hole transport layer / light-emitting layer / electron transport layer / charge generation layer / hole transport layer / light-emitting layer / electron transport layer.

[0056] Each of the above layers may be a single layer or multiple layers, and may be doped. In particular, the electron transport layer and the charge generation layer are preferably metal-doped layers doped with a metal, which can improve the electron transport ability and the ability to inject electrons into adjacent layers. In addition to the above layers, a protective layer (cap layer) may be further provided, which can further improve the luminous efficiency by the optical interference effect. The thickness of each layer is generally selected from the range of 1 nm to 200 nm, taking into consideration the resistance value of each layer material and the effect on the extraction efficiency of EL emission.

[0057] <Hole-transporting polymer compound> In the present invention, it is preferable that the organic EL layer contains a hole transporting polymer compound in order to improve adhesion to the substrate and prevent peeling. In particular, it is preferable that the first layer in contact with the substrate contains a hole transporting polymer compound. Here, the hole transporting property is a property that can efficiently transport holes required for recombination in the light emitting layer from the electrode. Therefore, the hole transporting compound is required to have a moderate ionization potential, a large hole mobility, excellent stability, and less generation of impurities that become traps during production or use. For example, the hole transporting compound preferably used in the present invention is preferably one having an ionization potential of 4.5 eV to 5.5 eV. In addition, the polymer compound is generally known to be composed of one or several types of repeating units and has an average molecular weight of about 10,000 or more.

[0058] As the hole transporting polymer compound of the present invention, for example, a polymer compound having a branched structure branched in three or more directions as described below and the following polymer compounds are preferable.

[0059] The hole transporting polymer compound in the present invention is preferably a polymer compound containing a repeating unit represented by the following formula (1).

[0060] [ka]

[0061] In formula (1), Ar a or Ar b each independently represents an aromatic hydrocarbon group or aromatic heterocyclic group having 4 to 60 carbon atoms which may have a substituent.

[0062] Examples of aromatic hydrocarbon ring groups include single rings or 2-5 condensed rings of 5- or 6-membered rings such as benzene ring, naphthalene ring, phenanthrene ring, anthracene ring, triphenylene ring, chrysene ring, naphthacene ring, perylene ring, coronene ring, acenaphthene ring, fluoranthene ring, and fluorene ring, each having one or two free valences, and rings in which a plurality of these rings are directly bonded. Here, in the present invention, the term "free valence" refers to a ring that can form a bond with another free valence, as described in Organic Chemistry and Biochemistry Nomenclature (Vol. 1) (revised 2nd edition, Nankodo, published in 1992). That is, for example, "a benzene ring having one free valence" refers to a phenyl group, and "a benzene ring having two free valences" refers to a phenylene group.

[0063] Examples of the aromatic heterocyclic group include a furan ring, a benzofuran ring, a thiophene ring, a benzothiophene ring, a pyrrole ring, a pyrazole ring, an imidazole ring, an oxadiazole ring, an indole ring, a carbazole ring, a pyrroloimidazole ring, a pyrrolopyrazole ring, a pyrrolopyrrole ring, a thienopyrrole ring, a thienothiophene ring, a furopyrrole ring, a furofuran ring, a thienofuran ring, and a benzisoxazole ring, each of which has one or two free valences. Examples of 5- or 6-membered heterocyclic rings include a single ring or 2-4 condensed rings such as a 5- or 6-membered heterocyclic ring, a benzisothiazole ring, a benzimidazole ring, a pyridine ring, a pyrazine ring, a pyridazine ring, a pyrimidine ring, a triazine ring, a quinoline ring, an isoquinoline ring, a cinnoline ring, a quinoxaline ring, a phenanthridine ring, a benzimidazole ring, a perimidine ring, a quinazoline ring, a quinazolinone ring, an azulene ring, and a triazine ring, and rings in which a plurality of these rings are directly bonded.

[0064] Here, when the aromatic hydrocarbon ring group or aromatic heterocyclic group is a condensed ring having one or two free valences, the number of the condensed monocyclic rings is preferably small in terms of high ring stability, preferably 8 or less, more preferably 5 or less. On the other hand, the lower limit is 2. Specifically, the aromatic hydrocarbon ring group or aromatic heterocyclic group is preferably a monocyclic ring such as a benzene ring, a thiophene ring, or a pyridine ring having one or two free valences; a condensed ring such as a naphthalene ring, an anthracene ring, a phenanthrene ring, a triphenylene ring, or a pyrene ring; and an aromatic hydrocarbon ring having 2 to 8 aromatic rings such as a fluorene ring, a biphenyl, or a terphenyl connected thereto, in terms of solubility and heat resistance. Among these, a group selected from a benzene ring, a fluorene ring, a biphenyl, and a terphenyl having one or two free valences is more preferable in terms of high solubility and high stability.

[0065] Examples of the substituent that the aromatic hydrocarbon ring group or aromatic heterocyclic group may have include saturated hydrocarbon groups having 1 to 20 carbon atoms, aromatic hydrocarbon ring groups having 6 to 25 carbon atoms, aromatic heterocyclic groups having 3 to 20 carbon atoms, diarylamino groups having 12 to 60 carbon atoms, alkyloxy groups having 1 to 20 carbon atoms, (hetero)aryloxy groups having 3 to 20 carbon atoms, alkylthio groups having 1 to 20 carbon atoms, (hetero)arylthio groups having 3 to 20 carbon atoms, cyano groups, etc. Among these, from the viewpoints of solubility and heat resistance, groups selected from saturated hydrocarbon groups having 1 to 20 carbon atoms and aromatic hydrocarbon ring groups having 6 to 25 carbon atoms are preferred.

[0066] Specifically, examples of saturated hydrocarbon groups having 1 to 20 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, iso-butyl, sec-butyl, tert-butyl, hexyl, octyl, cyclohexyl, decyl, and octadecyl groups, etc. Among these, from the viewpoints of availability of raw materials and low cost, methyl, ethyl, and isopropyl groups are preferred, and groups selected from methyl and ethyl groups are more preferred.

[0067] Examples of the monovalent aromatic hydrocarbon ring group having 6 to 25 carbon atoms include naphthyl groups such as phenyl group, 1-naphthyl group, and 2-naphthyl group; phenanthryl groups such as 9-phenanthryl group and 3-phenanthryl group; anthryl groups such as 1-anthryl group, 2-anthryl group, and 9-anthryl group; naphthacenyl groups such as 1-naphthacenyl group and 2-naphthacenyl group; chrysenyl groups such as 1-chrysenyl group, 2-chrysenyl group, 3-chrysenyl group, 4-chrysenyl group, 5-chrysenyl group, and 6-chrysenyl group; pyrenyl groups such as 1-pyrenyl group; triphenylenyl groups such as 1-triphenylenyl group; coronenyl groups such as 1-coronenyl group; biphenyl groups such as 4-biphenyl group and 3-biphenyl group; groups having a fluoranthene ring; groups having a fluorene ring; groups having an acenaphthene ring, and substituents having a benzpyrene ring or the like. Among these, a group selected from a phenyl group, a 2-naphthyl group, and a 3-biphenyl group is preferred from the viewpoint of the stability of the compound, and a phenyl group is particularly preferred from the viewpoint of ease of purification.

[0068] Examples of aromatic heterocyclic groups having 3 to 20 carbon atoms include thienyl groups such as 2-thienyl groups, furyl groups such as 2-furyl groups, imidazolyl groups such as 2-imidazolyl groups, carbazolyl groups such as 9-carbazolyl groups, pyridyl groups such as 2-pyridyl groups, and triazinyl groups such as 1,3,5-triazin-2-yl groups. Among these, carbazolyl groups, particularly 9-carbazolyl groups, are preferred from the viewpoint of stability.

[0069] Examples of the diarylamino group having 12 to 60 carbon atoms include a diphenylamino group, an N-1-naphthyl-N-phenylamino group, an N-2-naphthyl-N-phenylamino group, an N-9-phenanthryl-N-phenylamino group, an N-(biphenyl-4-yl)-N-phenylamino group, a bis(biphenyl-4-yl)amino group, etc. Among these, a group selected from a diphenylamino group, an N-1-naphthyl-N-phenylamino group, and an N-2-naphthyl-N-phenylamino group is preferred, and a diphenylamino group is particularly preferred from the viewpoint of stability.

[0070] Examples of the alkyloxy group having 1 to 20 carbon atoms include a methoxy group, an ethoxy group, an isopropyloxy group, a cyclohexyloxy group, and an octadecyloxy group. Examples of the (hetero)aryloxy group having 3 to 20 carbon atoms include a substituent having an aryloxy group such as a phenoxy group, a 1-naphthyloxy group, or a 9-anthranyloxy group, and a heteroaryloxy group such as a 2-thienyloxy group.

[0071] Examples of the alkylthio group having 1 to 20 carbon atoms include a methylthio group, an ethylthio group, an isopropylthio group, and a cyclohexylthio group.

[0072] Examples of the (hetero)arylthio group having 3 to 20 carbon atoms include arylthio groups such as a phenylthio group, a 1-naphthylthio group, and a 9-anthranylthio group, and heteroarylthio groups such as a 2-thienylthio group.

[0073] When the polymer compound has an arylamino structure in a repeating unit to which a group other than an aromatic hydrocarbon ring group or an aromatic heterocyclic group is bonded, the group other than an aromatic hydrocarbon ring group or an aromatic heterocyclic group is preferably an aliphatic hydrocarbon group having 1 to 70 carbon atoms and a heteroaliphatic hydrocarbon group having 1 to 70 carbon atoms. The heteroaliphatic hydrocarbon group refers to an aliphatic hydrocarbon group having a heteroatom. Examples of the heteroatom include a nitrogen atom and an oxygen atom. The aliphatic hydrocarbon group may be chain or cyclic, and may be saturated or unsaturated.

[0074] Examples of the aliphatic hydrocarbon group include methyl, ethyl, propyl, isopropyl, butyl, iso-butyl, sec-butyl, tert-butyl, hexyl, octyl, cyclohexyl, decyl, and octadecyl groups. Among these, from the viewpoints of availability and low cost of raw materials, groups having 1 to 10 carbon atoms, such as methyl, 1,2-ethyl, 1,3-propyl, 1,4-butyl, 1,5-pentyl, and 1,8-octyl, are preferred, and groups having 1 to 8 carbon atoms are more preferred. From the viewpoints of ease of synthesis, groups having 1 to 3 carbon atoms, such as methyl, ethyl, and isopropyl, are particularly preferred, and groups having 1 to 2 carbon atoms, such as methyl and ethyl. From the viewpoints of oxidation-reduction durability, the aliphatic hydrocarbon group is preferably a saturated hydrocarbon group.

[0075] The aliphatic unsaturated hydrocarbon group is preferably an alkenylene group, and specific examples thereof include a 1,2-vinylene group, a 1,3-propenylene group, a 1,2-propenylene group, and a 1,4-butenylene group. Among these, a vinylene group is particularly preferred because the improved planarity of the molecule leads to a broadening of the conjugated surface, and the charge is delocalized, which tends to increase the stability of the compound. The number of carbon atoms contained in the unsaturated aliphatic hydrocarbon group is preferably 2 or more from the viewpoint of planarity and the spread of the charge, and is preferably 10 or less, and more preferably 6 or less.

[0076] <Polymer compounds with a branched structure that branches in three or more directions> The "branched structure branched in three or more directions", which is one of the preferred embodiments of the hole-transporting polymer compound, is intended to include a structure formed by binding at least three second structural units to a first structural unit having three or more bonds via the above bonds.

[0077] The first structural unit is preferably a condensed polycyclic aromatic hydrocarbon group having three or more bonds. The condensed polycyclic aromatic hydrocarbon group from which the first structural unit is derived is a compound in which a plurality of aromatic rings are condensed, and since it is easy to obtain excellent charge transportability, it is preferable that three or more aromatic rings are present in the molecule. In consideration of the solubility of the charge transport material, the number of aromatic rings present in the molecule is preferably in the range of 3 to 6. The condensed polycyclic aromatic hydrocarbon may be one in which a plurality of aromatic rings are linearly linked or indirectly linked.

[0078] In a preferred embodiment, the condensed polycyclic aromatic hydrocarbon group that derives the first structural unit is preferably a group that includes at least one structure selected from the group consisting of anthracene, tetracene, pentacene, phenanthrene, chrysene, triphenylene, tetraphene, pyrene, picene, pentaphene, perylene, helicene, and coronene.Although not particularly limited, when the first structural unit includes a structural unit derived from pyrene, it is more preferable because it is easy to obtain excellent charge transportability and durability.

[0079] In a preferred embodiment, the second structural unit preferably includes at least one structure selected from the group consisting of an aromatic amine structure, a carbazole structure, a thiophene structure, a bithiophene structure, a p-phenylene structure, an m-phenylene structure, and a fluorene structure, because it is easy to obtain excellent charge transport properties.The second structural unit is preferably a polymer chain consisting of a monomer unit including these structures.In particular, it is more preferable to include at least one structure selected from the group consisting of an aromatic amine structure, a carbazole structure, a thiophene structure, and a bithiophene structure.

[0080] The polymeric compound can be synthesized by a method well known to those skilled in the art. Although not particularly limited, the polymeric compound can be produced, for example, by polymerizing various monomers including condensed polycyclic aromatic hydrocarbon monomers having three or more polymerizable sites in one molecule. Alternatively, the polymeric compound can be produced by forming linear polymeric compounds and then polymerizing them with each other. When the polymeric compound is a copolymer, the copolymer may be a random, block or graft copolymer, or a copolymer having an intermediate structure therebetween, for example, a random copolymer having block properties.

[0081] In one embodiment, the polymer compound is an oligomer or polymer obtained by reacting a first monomer compound containing the first structural unit with a second monomer compound containing the second structural unit. A method well known in the art can be applied to the reaction. For example, a Suzuki coupling reaction can be applied in which a Pd(0) or Pd(II) compound is used as a catalyst to generate a bond between a boronic acid and a halogen such as bromine. For a specific method of preparing a polymer compound using the Suzuki coupling reaction, the description in WO2010 / 140553 can be referred to.

[0082] <Preparation of hole-transporting polymer compound> Dissolving the hole transporting polymer compound in a solvent enables a wet film formation method, which is preferable in terms of thin film formation. The hole transporting polymer compound and, if necessary, other components can be mixed with an appropriate solvent to prepare a composition.

[0083] The solvent contained in the composition is not particularly limited, but is preferably a solvent that can dissolve the hole transport polymer compound at 0.1% by weight, more preferably 0.5% by weight, and even more preferably 1.0% by weight or more. The boiling point of the solvent is preferably 110°C or more, more preferably 140°C or more, even more preferably 180°C or more, and particularly preferably 200°C or more. The boiling point is preferably 400°C or less, and more preferably 300°C or less. If the boiling point of the solvent is too low, the drying speed is too fast, and the film quality may deteriorate. In addition, if the boiling point of the solvent is too high, the temperature of the drying process needs to be increased, which may have a negative effect on other layers and the substrate.

[0084] The solvent may be any solvent that satisfies the above-mentioned characteristics, and may be an ester solvent, an aromatic hydrocarbon solvent, an ether solvent, a halogen-containing organic solvent, an amide solvent, or the like. A solvent selected from an ester solvent, an aromatic hydrocarbon solvent, and an ether solvent is preferred because it has high solubility and has little adverse effect from residual solvent. Examples of the ester solvent include aliphatic esters such as ethyl acetate, n-butyl acetate, ethyl lactate, and n-butyl lactate, and aromatic esters such as phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, propyl benzoate, and n-butyl benzoate.

[0085] Examples of aromatic hydrocarbon solvents include toluene, xylene, methylene, cyclohexylbenzene, 3-isopropylbiphenyl, 1,2,3,4-tetramethylbenzene, 1,4-diisopropylbenzene, and methylnaphthalene.

[0086] Examples of the ether-based solvent include aliphatic ethers such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol-1-monomethyl ether acetate (PGMEA), and aromatic ethers such as 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, anisole, phenetole, 2-methoxytoluene, 3-methoxytoluene, 4-methoxytoluene, 2,3-dimethylanisole, and 2,4-dimethylanisole.

[0087] Examples of the halogen-containing organic solvent include 1,2-dichloroethane, chlorobenzene, and o-dichlorobenzene.

[0088] Examples of the amide solvent include N,N-dimethylformamide and N,N-dimethylacetamide.

[0089] In addition, dimethyl sulfoxide and the like can also be used.

[0090] These solvents may be used alone or in any combination and ratio of two or more. The amount of the solvent is preferably 10% by weight or more in the composition, more preferably 50% by weight or more, even more preferably 60% by weight or more, and particularly preferably 80% by weight or more. The amount of the solvent is preferably 99.99% by weight or less in the composition.

[0091] The amount of the hole transport polymer compound contained in the composition is preferably large in terms of increasing the viscosity of the composition, but is preferably small in terms of solubility.Therefore, specifically, the amount of the hole transport polymer compound contained in the composition is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and even more preferably 0.5% by weight or more.In addition, the amount of the hole transport polymer compound contained in the composition is preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 20% by weight or less.The composition may contain two or more types of hole transport polymer compounds, and in this case, the total of the two or more types is preferably within the above range.

[0092] <Compounds with a phenanthroline skeleton> In the present invention, in order to improve the adhesion in the organic EL layer and prevent peeling, the organic EL layer preferably contains a compound having a phenanthroline skeleton. The compound having a phenanthroline skeleton is preferably contained in the layers constituting the organic EL layer, particularly in the electron transport layer and the metal-doped layer.

[0093] The compound having a phenanthroline skeleton is preferably a compound having a heteroaryl ring structure containing an electron-accepting nitrogen atom, and a representative example thereof is a compound having a phenanthroline skeleton represented by the following general formula (2).

[0094] [ka]

[0095] Here, R 1 ~R 8 may be the same or different and are each independently selected from a hydrogen atom, an alkyl group, a cycloalkyl group, an alkenyl group, a cycloalkenyl group, an aryl group, a heteroaryl group, and a heterocyclic group.

[0096] Furthermore, in the present invention, it is preferable to contain a compound having a polymer of a phenanthroline skeleton. As a representative example, it is more preferable to contain a phenanthroline polymer compound having a plurality of phenanthroline skeletons represented by the following general formula (3), since it has excellent ability to form a charge-transfer complex with a metal.

[0097] [ka]

[0098] Here, R 9 ~R 16 may be the same or different, and each independently represents a hydrogen atom, an alkyl group, a cycloalkyl group, an alkenyl group, a cycloalkenyl group, an aryl group, a heteroaryl group, a heterocyclic group, X 1 where R 9 ~R 16 At least one of is X 1 m is a natural number between 2 and 6. X 1 X is a single bond or a linking unit that links m phenanthroline skeletons. 1 is preferably a single bond, an m-valent aromatic group, an m-valent aromatic heterocyclic group, an m-valent aliphatic group, or an m-valent group formed by combining these, and more preferably an m-valent aromatic group. Among the m-valent aromatic groups, an m-valent group derived from a benzene ring, a biphenyl ring, or a naphthalene ring is preferred, and an m-valent group derived from a benzene ring is more preferred. In addition, from the viewpoint of the thermal stability of the material, m is preferably 2 or 3, and more preferably 2.

[0099] R shown in general formula (2) and general formula (3) 1 ~R 16Among the substituents, the alkyl group refers to a saturated aliphatic hydrocarbon group such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, or a tert-butyl group, which may or may not have a substituent. When substituted, the additional substituent is not particularly limited, and examples thereof include an alkyl group, a halogen, an aryl group, and a heteroaryl group, which is also common to the following description. The number of carbon atoms in the alkyl group is not particularly limited, but is preferably 1 to 20, more preferably 1 to 8, in terms of availability and cost. The cycloalkyl group refers to a saturated alicyclic hydrocarbon group such as a cyclopropyl group, a cyclohexyl group, a norbornyl group, or an adamantyl group, which may or may not have a substituent. The number of carbon atoms in the alkyl group is not particularly limited, but is preferably 3 to 20.

[0100] The alkenyl group refers to an unsaturated aliphatic hydrocarbon group containing a double bond, such as a vinyl group, an allyl group, or a butadienyl group, which may be unsubstituted or substituted. The cycloalkenyl group refers to an unsaturated alicyclic hydrocarbon group containing a double bond, such as a cyclopentenyl group, a cyclopentadienyl group, or a cyclohexene group, which may be unsubstituted or substituted. The alkynyl group refers to an unsaturated aliphatic hydrocarbon group containing a triple bond, such as an acetylenyl group, which may be unsubstituted or substituted. The alkoxy group refers to an aliphatic hydrocarbon group connected via an ether bond, such as a methoxy group, which may be unsubstituted or substituted. The alkylthio group refers to an alkoxy group in which the oxygen atom of the ether bond is replaced by a sulfur atom. The aryl ether group refers to an aromatic hydrocarbon group connected via an ether bond, such as a phenoxy group, which may be unsubstituted or substituted. The arylthioether group refers to an aryl ether group in which the oxygen atom of the ether bond is replaced by a sulfur atom. The aryl group refers to an aromatic hydrocarbon group such as a phenyl group, a naphthyl group, a biphenyl group, a phenanthryl group, a terphenyl group, or a pyrenyl group, which may be unsubstituted or substituted. Furthermore, the heteroaryl group refers to a cyclic aromatic group having one or more atoms other than carbon in the ring, such as a pyridyl group, a furanyl group, a thiophenyl group, a quinolinyl group, an isoquinolinyl group, a pyrazinyl group, a pyrimidyl group, a pyridazinyl group, a triazinyl group, a naphthyridinyl group, a cinnolinyl group, a phthalazinyl group, a quinoxalinyl group, a quinazolinyl group, a benzofuranyl group, a benzothiophenyl group, an indolyl group, a dibenzofuranyl group, a dibenzothiophenyl group, a carbazolyl group, a benzocarbazolyl group, a carbolinyl group, an indolocarbazolyl group, a benzofurocarbazolyl group, a benzothienocarbazolyl group, a dihydroindenocarbazolyl group, a benzoquinolinyl group, an acridinyl group, a dibenzoacridinyl group, a benzimidazolyl group, an imidazopyridyl group, a benzoxazolyl group, a benzothiazolyl group, or a phenanthrolinyl group.Here, the naphthyridinyl group refers to any of 1,5-naphthyridinyl group, 1,6-naphthyridinyl group, 1,7-naphthyridinyl group, 1,8-naphthyridinyl group, 2,6-naphthyridinyl group, and 2,7-naphthyridinyl group. The heteroaryl group may or may not have a substituent. The number of ring-forming atoms is not particularly limited, but is preferably in the range of 3 to 40, more preferably 3 to 30. In addition, the heterocyclic group refers to an aliphatic ring having an atom other than carbon in the ring, such as a pyran ring, a piperidine ring, and a cyclic amide, which may or may not have a substituent. The number of carbon atoms in the heterocyclic group is not particularly limited, but is preferably in the range of 2 to 20.

[0101] In addition, the substituent itself has a three-dimensional structure, or the steric repulsion between the phenanthroline skeleton or adjacent substituents brings about a three-dimensional structure, so that the compound containing the phenanthroline skeleton has low planarity and is less likely to crystallize, and can maintain a good amorphous thin film state. The substituent itself has a three-dimensional structure, for example, a t-butyl group, an adamantyl group, a norbornyl group, etc., which is not a two-dimensional planar structure, and may be unsubstituted or substituted. In addition, the substituent that brings about a three-dimensional structure due to the steric repulsion between the phenanthroline skeleton or adjacent substituents, such as an α-naphthyl group, a phenanthrene group, or a mesityl group, indicates that even if the substituent itself has a planar structure, the substituent plane is in a different plane from the phenanthroline skeleton plane due to the steric repulsion between the substituent and the phenanthroline skeleton or between the substituent and adjacent substituents. These can be considered using molecular models, computer chemistry, etc.

[0102] Furthermore, by linking a plurality of phenanthroline skeletons or polymerizing them, the compound containing the phenanthroline skeleton has a high molecular weight and a high glass transition temperature, which also makes crystallization less likely to occur and allows the compound to maintain a good amorphous thin film state, which is more preferable.

[0103] In the compound having a phenanthroline skeleton of the general formula (2) of the present invention, R 1 , R 3 , R 6 or R 8 From the viewpoint of chemical stability of the compound, improving electron mobility, and enabling lower voltage operation, it is more preferable to introduce a substituent at the carbon atom adjacent to the nitrogen atom, i.e., R 1 and R 8 It is more preferable to introduce a substituent at the position. The substituents are the same as those described above, but the substituents introduced at these positions are preferably an alkyl group, an aryl group, or a heteroaryl group, and more preferably an aryl group. Among the aryl groups, a phenyl group, a naphthyl group, or a fluorenyl group is preferable, and a phenyl group is more preferable.

[0104] In the phenanthroline polymer represented by the general formula (3) of the present invention, R 9 , R 11 , R 14 or R 16 From the viewpoint of chemical stability of the compound and of improving electron mobility to enable lower voltage operation, it is preferable to introduce a substituent at the carbon atom adjacent to the nitrogen atom, i.e., R 9 and R 16 It is more preferable to introduce a substituent at the position. The substituents are the same as those described above, but the substituents introduced at these positions are preferably groups selected from an alkyl group, an aryl group, and a heteroaryl group, and more preferably an aryl group. Among the aryl groups, groups selected from a phenyl group, a naphthyl group, and a fluorenyl group are preferable, and more preferably a phenyl group.

[0105] Specific examples of the compound having a phenanthroline skeleton include those having the following structures, but are not limited thereto.

[0106] [ka]

[0107] [ka]

[0108] [ka]

[0109] [ka]

[0110] The organic EL device materials represented by the general formula (2) and the general formula (3) can be synthesized by a known synthesis method, for example, a coupling reaction between an aryl halide derivative and an arylboronic acid derivative using palladium, but is not limited thereto.

[0111] <Compounds having a terpyridine skeleton> In the present invention, in order to improve the adhesion in the organic EL layer and prevent peeling, the organic EL layer preferably contains a compound having a terpyridine skeleton. The compound having a terpyridine skeleton is preferably used in the layers constituting the organic EL layer, particularly in the electron transport layer and the metal-doped layer.

[0112] As a compound having a terpyridine skeleton, it is preferable to use a compound having a heteroaryl ring structure containing an electron-accepting nitrogen. As a representative example, a compound having a terpyridine skeleton represented by the following general formula (4) is preferable. The terpyridine skeleton is a skeleton in which three pyridine rings are bonded in succession, and when doped with a metal, for example, it has a high coordination ability with the metal and is easy to form a charge transfer complex. If one terpyridine skeleton is contained in a molecule, it functions as a host material, but it is more preferable to contain two or more. In addition, as a result of focusing on the effects of a phenanthrolinyl group, a terpyridyl group, and their linking groups, a compound having a terpyridine skeleton represented by the following general formula (4) is preferable.

[0113] [ka]

[0114] In general formula (4), L 1 is a substituted or unsubstituted phenylene group, a substituted or unsubstituted naphthylene group, or a substituted or unsubstituted anthrylene group; L 2 is a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted naphthylene group, or a substituted or unsubstituted anthrylene group. 1 In the case where is substituted, the substituent is an alkyl group or an alkoxy group. These substituents are preferable because they can improve the stability of the compound without decreasing the charge transport property of the compound.

[0115] In the general formula (4), X 2 ~X 4 One of the groups is a nitrogen atom, and the others are methine groups. From the viewpoint of increasing the coordination with the metal atom and forming a more stable layer, X 4 is preferably a nitrogen atom. By forming a more stable layer, it is possible to operate at a low voltage and to further improve the durability and life span.

[0116] In the general formula (4), n is 0 or 1. When n is 1, A is a phenyl group or a pyridyl group. When n is 1, the highly reactive 2- and 9-positions of the substitution positions of the phenanthroline are substituted, so that the stability of the compound can be improved. Furthermore, by selecting a phenyl group or a pyridyl group as A, a layer with higher metal coordination and higher stability can be formed when used in a metal doping layer due to the high coordination of the nitrogen atom on the phenanthrolinyl group. Therefore, the driving voltage can be further reduced and the durability life can be improved. From the viewpoint of further improving the stability and durability life of the element, a phenyl group is preferable as A.

[0117] In general formula (4), when n is 0, the 9-position of phenanthroline is hydrogen. When n is 0, phenanthroline is sterically unoccupied, and therefore when used in a metal doping layer, it is possible to form a layer with higher metal coordination and more stable properties.

[0118] In general formula (4), L 1 A phenylene group, a naphthylene group or an anthrylene group is selected as L 2 By selecting a single bond, a phenylene group, a naphthylene group, or an anthrylene group as L, it is possible to easily conjugate the phenanthrolinyl group, the terpyridyl group, and the linking group thereof, and to increase the charge transportability of the entire compound. Therefore, when used in an organic EL device, the driving voltage can be reduced and the luminous efficiency can be improved. In addition, since the coordination to metal atoms can be improved, when the compound represented by the general formula (4) is used in a metal-doped layer in an organic EL device, a stable layer can be formed. From the viewpoint of increasing the film quality stability and further improving the luminous efficiency and durable life, L 1 or L 2 is preferably a naphthylene group. 2 When is a single bond, the interaction between the phenanthrolinyl group and the terpyridyl group can be made greater, and the luminous efficiency and durable life can be further improved.

[0119] From the viewpoint of suppressing crystallization and improving the stability of the film quality, the molecular weight of the compound represented by general formula (4) is preferably 400 or more. On the other hand, from the viewpoint of improving processability during sublimation purification and vapor deposition, the molecular weight of the compound represented by general formula (4) is preferably 640 or less.

[0120] Examples of the compound represented by the above general formula (4) include the compounds shown below. Note that the following are merely examples, and compounds other than those explicitly described here can also be preferably used as long as they are represented by general formula (4).

[0121] [ka]

[0122] [ka]

[0123] [ka]

[0124] [ka]

[0125] The organic EL device material represented by the general formula (4) can be synthesized by a known synthesis method, for example, a coupling reaction between an aryl halide derivative and an arylboronic acid derivative using palladium, but is not limited thereto.

[0126] <Light-emitting layer> In the light-emitting layer, the injected electrons and holes recombine to emit light. A major feature of organic EL displays is that they can emit a variety of colors by selecting the materials that make up this light-emitting layer.

[0127] The light-emitting layer is a layer in which the light-emitting material is excited by the recombination energy due to the collision of holes and electrons, and emits light. The light-emitting layer may be a single layer, or may be composed of a plurality of layers stacked together. The light-emitting layer is formed of a light-emitting material (host material and / or dopant material). Each light-emitting layer may be composed of only one of the host material or the dopant material, or may be composed of a combination of one or more host materials and one or more dopant materials. That is, in each light-emitting layer, only the host material or the dopant material may emit light, or both the host material and the dopant material may emit light. From the viewpoint of efficiently utilizing electric energy and obtaining light emission with high color purity, it is preferable that the light-emitting layer is composed of a combination of a host material and a dopant material. The dopant material may be contained in the entire light-emitting layer, or may be contained in a part of the light-emitting layer.

[0128] The content of the dopant material in the light-emitting layer is preferably 30 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the host material, from the viewpoint of suppressing concentration quenching.

[0129] The light-emitting layer can be formed by a method of co-evaporating a host material and a dopant material, or a method of previously mixing a host material and a dopant material and then vapor-depositing the mixture.

[0130] Examples of host materials constituting the light-emitting layer include compounds having condensed aryl rings such as naphthalene, anthracene, phenanthrene, pyrene, chrysene, naphthacene, triphenylene, perylene, fluoranthene, fluorene, and indene. Two or more of these may be used. As hosts used when the light-emitting layer emits triplet light (phosphorescence), metal chelated oxinoid compounds, dibenzofuran derivatives, dibenzothiophene derivatives, carbazole derivatives, indolocarbazole derivatives, triazine derivatives, and triphenylene derivatives are preferably used. Among these, compounds having an anthracene skeleton or a pyrene skeleton are more preferable because they are more likely to emit light with high efficiency.

[0131] Examples of dopant materials constituting the light-emitting layer include condensed ring derivatives such as anthracene and pyrene, metal complex compounds such as tris(8-quinolinolato)aluminum, bisstyryl derivatives such as bisstyryl anthracene derivatives and distyrylbenzene derivatives, tetraphenylbutadiene derivatives, dibenzofuran derivatives, carbazole derivatives, indolocarbazole derivatives, and polyphenylenevinylene derivatives. As dopant materials used when the light-emitting layer emits triplet light (phosphorescence), metal complex compounds containing at least one metal selected from the group consisting of iridium (Ir), ruthenium (Ru), palladium (Pd), platinum (Pt), osmium (Os), and rhenium (Re) are preferred. The ligands constituting the metal complex compounds can be appropriately selected based on the required light emission color, organic EL display device performance, and relationship with the host compound, and preferably have a nitrogen-containing aromatic heterocycle such as a phenylpyridine skeleton, a phenylquinoline skeleton, or a carbene skeleton. Specific examples include tris(2-phenylpyridyl)iridium complex, bis(2-phenylpyridyl)(acetylacetonate)iridium complex, tetraethylporphyrin platinum complex, etc. Two or more of these may be used.

[0132] <Second electrode> In the present invention, the second electrode 6 is preferably a light-reflective electrode in the case of a bottom emission type, and a light-transmitting electrode in the case of a top emission type.

[0133] When the second electrode is a bottom emission type, a material that shows high reflectance of visible light at a certain film thickness and low electrical resistance is preferable, and Ag or an Ag alloy film mainly containing Ag is useful because of its high reflectance. As the Ag alloy film, an MgAg alloy mainly containing Ag can be used. In addition, an Al alloy film mainly containing Al is also good as a second electrode for bottom emission. An AlCr alloy film containing Cr and an AlNi alloy film containing Ni are preferable because they have a high reflectance comparable to that of pure Al and can realize low electrical resistance.

[0134] When the second electrode is a top-emission type, the material can be, for example, a conductive metal oxide such as transparent tin oxide, indium oxide, or indium tin oxide (ITO). In order to avoid damage to the organic EL layer, a thin film of an MgAg alloy that can be produced by vapor deposition is preferable.

[0135] The resistance of the second electrode is not limited as long as it can supply a sufficient current for the light emission of the light emitting element, as with the first electrode, but it is desirable that the resistance be low from the viewpoint of the power consumption of the light emitting element. The thickness of the second electrode can be selected arbitrarily according to the characteristics such as transmittance and resistance value, but it can be between 100 nm and 300 nm for a bottom emission type and between 10 nm and 30 nm for a top emission type.

[0136] <Wiring, TFT> In the present invention, as described above, the base material 1 may include wiring and a driving circuit such as the TFT 7.

[0137] When the organic EL display device is of an active driving top emission type, the patterned island-shaped first electrode 2 is often connected to a TFT that is formed in advance as part of the substrate 1 .

[0138] The semiconductor layer of a TFT can be made of a-Si (amorphous silicon), p-Si (polycrystalline silicon), microcrystalline silicon, oxides such as In-Ga-Zn-O, and LTPO (Low Temperature Polycrystalline Oxide), which combines p-Si and oxide. TFTs can be roughly classified into bottom-gate and top-gate types in terms of structure. It is preferable to use the bottom-gate type for a-Si TFTs and the top-gate type for p-Si TFTs. For example, in the case of a top-gate type, a drain electrode and a source electrode are connected to the semiconductor layer, and a gate electrode is provided above the semiconductor layer. TFTs are formed on a substrate by repeating the elemental steps of thin film formation, patterning, etching, and cleaning several times. Known methods can be used to form TFTs.

[0139] <Planarization layer> For example, as shown in FIG. 2, when wiring and TFTs 7 are provided inside the substrate 1 such as an active driving type, it is preferable to provide a planarization layer 8 on the substrate. By providing a planarization layer, the planarization layer covers the unevenness of the wiring and TFTs, and the substrate can be planarized. In this case, since the first electrode 2 is provided on the planarization layer, it is preferable that the first electrode and the wiring and TFTs are connected through a contact hole formed in the planarization layer. The material of the planarization layer is not limited to either a known organic substance or an inorganic substance, but it is preferable to include a cured film of a photosensitive resin composition from the viewpoint of processability. As a method for forming the planarization layer, a known method can be used. Among them, wet coating methods such as spin coating, slit coating, dip coating, spray coating, and printing, which can uniformly form a thin film on a large substrate, are preferable.

[0140] <Sealing layer> After the second electrode 6 is formed, it is preferable to seal the organic EL display device with a sealing layer. This is because light-emitting elements are considered to be vulnerable to oxygen and moisture, and therefore, in order to obtain a highly reliable display device, it is preferable to perform sealing in an atmosphere with as little oxygen and moisture as possible. It is also preferable to select a material with high gas barrier properties for use in the sealing layer, and, like the substrate 1, it is appropriately selected from glass, resin films, gas barrier films, and the like. For example, an example of a gas barrier film is SiO 2 (silicon oxide), SiN (silicon nitride), and SiON (silicon oxynitride). 2 A sealing layer made of a resin material such as an acrylic resin or a silicone resin may be provided on a layer made of a material such as silicon oxide (SiO2), silicon nitride (SiN), silicon oxynitride (SiON), etc. In the case of a top-emission display device, the sealing layer is preferably made of a light-transmitting material.

[0141] Furthermore, when bonding is required, the adhesive used must have high gas barrier properties. This can be selected from commonly known adhesives such as a two-component epoxy adhesive (XNR, manufactured by Nagase ChemteX Corporation) or an encapsulant for organic devices (Moisture Cut, manufactured by MORESCO Corporation). Alternatively, a method in which frit glass is melted with a laser around the periphery of the display device and bonded can also be used.

[0142] As a further consideration to moisture, it is also effective to introduce a desiccant in the sealing process. Known desiccants include barium oxide and calcium oxide, but there is no particular limitation as long as they have high moisture adsorption performance.

[0143] <Manufacturing method for organic EL display device> The organic EL display device of the present invention is an organic EL display device having a substrate, an organic EL layer, and a second electrode, the substrate having a first electrode, a pixel division layer, and a spacer having an inverse tapered shape on a base material, and a part of the spacer having an inverse tapered shape is embedded in the pixel division layer. An example of a manufacturing method of the organic EL display device of the present invention will be described using the case of manufacturing a top emission type organic EL display device shown in FIG. 9 as an example.

[0144] First, wiring and a TFT 7 are provided on the base 1a of the substrate, which is a resin film. In addition to the TFT formation steps such as the "gate electrode formation step," the "gate insulating film formation step," the "Si film formation step," and the "source and drain electrode formation step," wiring is provided to ensure electrical connection, but all of these steps can be formed using known methods.

[0145] Next, the composition for forming the planarization layer 8 is applied by a slit coating method or the like to form a film, and is then heated and cured to form the planarization layer 8. At this time, contact holes for the purpose of connecting to the first electrode 2 are provided in the planarization layer 8. If the composition for forming the planarization layer is photosensitive, the contact holes can be provided by photolithography processing, and if it is not photosensitive, the contact holes can be provided by general etching processing using a resist material as a mask. In this manner, the substrate 1 is completed.

[0146] Next, AgPdCu and ITO are formed in this order on the substrate, and then patterned to obtain the first electrode 2.

[0147] After the first electrode 2 is formed, the pixel division layer 3 is formed on the substrate. The pixel division layer forming composition is applied to the substrate, formed into a film, and cured by heating to form the pixel division layer 3. A wet coating method is preferable as a method for applying the composition. Examples of the wet coating method include spin coating, slit coating, dip coating, spray coating, and printing. At this time, the pixel division layer is processed to provide openings in the pixel division layer on the first electrode 2. The openings become display pixels in the organic EL display device. If the pixel division layer forming composition is photosensitive, the openings can be provided by photolithography processing, and if it is not photosensitive, the openings can be provided by general etching processing using a resist material as a mask.

[0148] Furthermore, a spacer 4 having an inverse tapered shape is provided so that a part of the spacer is embedded in the pixel dividing layer 3. The shape of the inverse tapered spacer, which is a feature of the organic EL display device of the present invention, can be adjusted by the processing method. The material of the spacer is not limited to either a known organic or inorganic material, but it is preferable to use a negative type photosensitive resin composition in order to easily achieve the inverse tapered shape.

[0149] Methods for forming a spacer having an inverse tapered shape include, for example, (A) a method using a negative photosensitive resin composition, (B) a method using a positive photosensitive resin composition having an image inversion function, and (C) a method using a positive photosensitive resin composition and focus adjustment of an exposure machine.

[0150] (A) Method using a negative-type photosensitive resin composition In this method, a negative photosensitive resin composition is applied to the entire surface of the substrate on which the pixel division layer is formed, and then prebaked, and a photomask is placed on top of the substrate, and ultraviolet light is irradiated through the transparent portion of the photomask. In the exposed area where ultraviolet light hits through the opening of the photomask, the photosensitive resin composition is exposed to light and becomes insoluble in the developer. During this exposure process, a phenomenon occurs in which the exposure intensity decreases in the direction of the depth of the film thickness according to the light absorption of the photosensitive resin composition.

[0151] Therefore, when the prebaked film is developed after exposure, the outermost surface of the non-exposed region (alkali-soluble region) dissolves in the developer in the early stage of development, and dissolution also progresses laterally along the direction of the film thickness. In this way, a spacer having an inverse tapered shape can be obtained. Therefore, for example, the photosensitive resin composition preferably contains a material that absorbs ultraviolet light, and in the present invention, it is preferable that the photosensitive resin composition contains a coloring material as described above.

[0152] (B) Method using a positive-type photosensitive resin composition having an image reversal function This method is also called the image reversal process, and uses, for example, the AZ5200E series manufactured by Hoechst as a photosensitive resin composition. This photosensitive resin composition is a positive-type photosensitive resin composition, which is a mixture of an alkali-soluble phenolic resin and naphthoquinone diazide, to which a negative-working agent such as a basic amine is added to impart an image reversal function.

[0153] In this method, the photosensitive resin composition is applied to the entire surface of the substrate on which the pixel division layer is formed, and then prebaked, and a photomask is placed on top of the composition, and ultraviolet light is irradiated through the light-transmitting portion of the photomask. In this case, if the exposure dose is set to a low level and ultraviolet light is applied, the exposure intensity distribution in the exposed region of the photosensitive resin composition becomes lower the deeper in the film thickness direction due to the light absorption of the photosensitive resin composition itself, and the width of the exposed region (alkali-soluble region) becomes narrower the deeper in the film thickness direction. Conversely, the width of the non-exposed region of the photosensitive resin composition becomes wider the deeper in the film thickness direction. Subsequently, when the photosensitive resin composition is subjected to reversal baking and then exposed to light over the entire surface, a phenomenon occurs in which the alkali-soluble region and the alkali-insoluble region of the photosensitive resin composition are inverted. Therefore, when the photosensitive resin composition is immersed in a developer and developed, a spacer having an inverse tapered shape is obtained.

[0154] (C) A method using focus adjustment of an exposure machine with a positive-type photosensitive resin composition In this method, a positive photosensitive resin composition is applied to the entire surface of a substrate on which a pixel dividing layer is formed, and then pre-baked, and a photomask is placed over the substrate, and ultraviolet light is irradiated through the light-transmitting portion of the photomask. The focus position during this exposure is shifted toward the light source side from the best focus position.

[0155] As the focus position during exposure shifts from the best focus position to the side opposite the light source, the cross-sectional shape of the photosensitive resin composition pattern deteriorates from the top of the pattern cross section, whereas when the focus position shifts toward the light source side, the cross-sectional shape of the pattern deteriorates from the bottom of the pattern. Therefore, by shifting the focus position during exposure toward the light source side, a photosensitive resin composition pattern having an inverse tapered shape can be formed.

[0156] This phenomenon is particularly prominent in the standing wave effect of naphthoquinone diazide novolac-based positive-tone photosensitive resin compositions, which are superior in chemical stability, line width controllability, and handling properties to negative-tone photosensitive resin compositions and positive-tone photosensitive resin compositions with image reversal function.

[0157] Although such a method can be used to form a spacer having an inverse tapered shape, in the present invention, it is necessary to form a structure in which a part of the spacer is embedded in the pixel division layer. As a method for forming such a structure, for example, a method of forming a concave structure at a predetermined position of the pixel division layer and aligning the concave structure to form a spacer is available. As a method for forming a concave structure in the pixel division layer, a processing method such as dry etching or wet etching can be selected. In addition to the etching rate, the depth and taper angle of the concave structure may be adjusted by selecting the isotropic or anisotropic condition. In addition, when the bottom end of the spacer is brought into contact with the substrate, the pixel division layer may be coated and processed after the spacer having an inverse tapered shape is provided first.

[0158] Other processing methods for providing a concave structure in the pixel division layer include mechanical polishing using an abrasive, shot blasting or wet blasting using an abrasive, plasma discharge treatment, RIE, and other methods that can be used in combination. Since the light-emitting element is vulnerable to oxygen and moisture, it is preferable to select a dry process, and the process can be selected from glow discharge treatment, plasma discharge treatment, RIE, UV / ozone treatment, and the like. In particular, dry processes using a highly reactive atmosphere such as oxygen have a large effect on surface roughness, and RIE is preferable because it is easy to adjust the shape.

[0159] Subsequently, there is a step of forming the organic EL layer 5. Each layer constituting the organic EL layer 5, such as a hole transport layer, a light emitting layer, and an electron transport layer, can be formed by a known method. For example, they can be formed by a vacuum deposition method or an ink jet method. Among these, a wet coating method is preferable as a method for forming a layer using a hole transport polymer compound preferably used in the present invention. Examples of the wet coating method include a spin coating method, a slit coating method, a dip coating method, a spray coating method, and a printing method. A particularly preferable film formation method will be described later. On the other hand, a vacuum deposition method is preferable as a method for forming a layer using a compound having a phenanthroline skeleton or a compound having a terpyridine skeleton preferably used in the present invention.

[0160] When patterning is required in the organic EL layer, for example, a mask deposition method, which is one of the vacuum deposition methods, can be used. The mask deposition method is a method of patterning using a deposition mask, for example, a deposition mask with openings of a desired pattern is placed on the deposition source side of the substrate, and the organic EL layer is deposited.

[0161] Patterning by mask deposition or inkjet printing becomes more difficult as the pattern becomes finer. For this reason, for example, patterning is performed only on the minimum necessary layers, such as the light-emitting layer that determines the emitted color, and layers other than the light-emitting layer, such as the hole transport layer, electron transport layer, and metal-doped layer, are deposited on the entire surface, thereby improving panel yield and reducing costs.

[0162] After the organic EL layer 5 is formed, the second electrode 6 is further formed. The second electrode 6 can be formed by a known method, but a vacuum deposition method is preferable because it is easy to avoid deterioration or damage to the organic EL layer 5 that serves as the base.

[0163] In the method for manufacturing the top emission type organic EL display device of Fig. 9, after the step of forming the second electrode 6, the sealing layer 9, the polarizing layer 10, and the ultraviolet absorbing layer 11 are laminated in this order. Each layer can be formed by a known method. In this manner, the top emission type organic EL display device of Fig. 9 is completed.

[0164] <Method for forming a film of a hole-transporting polymer compound> As a method for forming an organic EL layer, particularly using a hole transporting polymeric compound, it is preferable to apply a composition containing a hole transporting polymeric compound using a wet coating method. As a coating method, the following methods are preferable. For example, methods such as spin coating, dip coating, die coating, bar coating, blade coating, roll coating, spray coating, capillary coating, inkjet printing, nozzle printing, screen printing, gravure printing, and flexographic printing can be adopted.

[0165] The temperature during film formation is preferably 10° C. or higher and 50° C. or lower, from the viewpoint of preventing film defects due to crystals generated in the composition. The relative humidity during film formation is not limited as long as it does not significantly impair the effects of the present invention, but is preferably 0.01 ppm or higher and 80% or lower.

[0166] In forming a film, after the composition is applied, the solvent is removed by heating or the like, but before the above-mentioned process, the coating film may be dried by heating, drying under reduced pressure, or the like to obtain a dry film. Examples of heating means include infrared heating, a hot plate, a clean oven, and the like. Specifically, for example, a dry film can be obtained by heating the substrate by irradiating infrared rays with an IR heater, placing the substrate on which the coating film is formed on a hot plate, or heating in an oven. In drying under reduced pressure, a dry film can be obtained by placing the substrate on which the coating film is formed in a decompressor and reducing the pressure. EXAMPLES

[0167] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. In each evaluation below, if the test number n is not specified, the evaluation was performed with n=1.

[0168] <Pixel division layer and spacer design> The design of the first electrodes, pixel dividing layers, and spacers of the substrates used in the emission color mixing test and bending reliability test described below will be explained with reference to the schematic diagrams of Figures 10 and 11. First, 100 first electrodes 2 were fabricated in stripes on a substrate 1 (100 mm x 100 mm) with a line width (W1) of 60 μm, a pitch of 100 μm, and a length of 10 mm. In other words, the exposed portions of the substrate 1 not covered by the first electrodes 2 at this point were stripes 40 μm wide.

[0169] Aligned with the center of this exposed portion, pixel division layer 3 was produced in a stripe shape with 101 lines, with a line width (W2) of 60 μm, a pitch of 100 μm, and a length of 10 mm. A recessed structure was formed by etching the center of the pixel division layer with a line width of 60 μm. Aligned with the center of this recessed structure, spacer 4 was produced in a stripe shape with a line width (W3) of 20 μm, a pitch of 100 μm, and a length of 10 mm. In this way, a striped substrate was obtained in which a structure of pixel opening 40 μm, pixel division section 20 μm, spacer section 20 μm, and pixel division section 20 μm was repeated 100 times.

[0170] <Spacer structure observation> The structure, taper angle, film thickness, and embedment depth of the spacer in each example and comparative example were evaluated by observing the cross section of the organic EL display device used in the emission color mixing test and bending reliability test described later. Specifically, a cross section was prepared by a focused ion beam (FIB) method using SMI3200SE manufactured by SIINT and FB-2000A μ-Sampling System manufactured by Hitachi High-Tech Corporation, and the cross section was observed with a transmission electron microscope (H-9000UHR manufactured by Hitachi High-Tech Corporation). The accelerating voltage for observation with the transmission electron microscope was 300 kV. Among the evaluation items, the spacer structure was evaluated as A to F as follows. A schematic diagram showing the spacer structure is shown in FIG. 12. A: The taper angle of the exposed part of the spacer is inverse taper, and the taper angle of the embedded part of the spacer is inverse taper. The relationship between the embedding depth T2 (μm) at which part of the spacer is embedded in the pixel division layer and the film thickness T3 (μm) of the pixel division layer is T3 = T2 B: The taper angle of the exposed spacer part is reverse taper, and the taper angle of the embedded spacer part is forward taper, and T3 = T2 C: The taper angle of the exposed spacer part is reverse taper, and the taper angle of the embedded spacer part is reverse taper, and T3>T2 D: The taper angle of the exposed spacer is reverse taper, and there is no embedded spacer (T2=0) E: The taper angle of the exposed spacer is forward tapered, and there is no embedded spacer (T2=0) F: No spacer.

[0171] <Light Mixing Test> In the driving voltage test in each of the examples and comparative examples, a first electrode and a second electrode were arbitrarily selected in the organic EL display device produced in each of the examples and comparative examples described below, and a driving voltage of 10 mA / cm was applied. 2 The device was driven with a direct current of 1000 V and the light emission was observed under a microscope. A source meter (2400, Keithley Instruments, Inc.) was used for the direct current drive, and a digital microscope (VHX-6000, Keyence, Inc.) was used for observation. The device was rated as A when the diffused light did not reach adjacent pixels, and B when it did.

[0172] <Bending reliability test> The bending reliability test of the organic EL display device in each example and comparative example was performed using the organic EL display device manufactured in each example and comparative example described later. As shown in FIG. 13, a metal cylinder 12 having a diameter of 5 mm was fixed to the center of the surface opposite to the surface on which the light emitting element was formed of the substrate 1 (100 mm×100 mm) on which the light emitting element was formed. After repeatedly bending the organic EL display device 1000 times along the cylinder 12 within a range from an embrace angle of 0° (substrate in a flat state) to an embrace angle of 180° (substrate folded back on the cylinder), the folded portion of the organic EL display device was observed under a microscope. In this observation, peeling of the spacer from the pixel division layer and peeling of the organic EL layer from the substrate were evaluated separately, and the number of peeling defects in 100 stripe-shaped patterns was counted (maximum 100). The result with the smallest number of peeling defects among the 10 tests was adopted, and specifically, it was evaluated as follows, A to H. Test A (spacer peeled off from pixel division layer) A: 0 (no peeling) B:1~9 pieces C: 10~19 pieces D: 20~39 pieces E: 40-59 bottles F: 60~79 pieces G:80~99 pieces H: 100 pieces (total number) Test B (peeling of organic EL layer from substrate) A: 0 (no peeling) B:1~9 pieces C: 10~19 pieces D: 20~39 pieces E: 40-59 bottles F: 60~79 pieces G:80~99 pieces H: 100 pieces (total number).

[0173] <Preparation of Photosensitive Resin Composition> Photosensitive resin compositions R-1 to R-5 used in each of the Examples and Comparative Examples were prepared as follows: Among the compounds used, the names of those using abbreviations are shown below. BAHF: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane BYK-333: Silicone surfactant BYK-333 (manufactured by BYK-Chemie) DFA: N,N-Dimethylformamide dimethyl acetal DPCA-60: Caprolactone 6 mole modified dipentaerythritol hexaacrylate (hexafunctional acrylate having six pentyleneoxy chains, manufactured by Nippon Kayaku Co., Ltd.) GBL: gamma-butyrolactone MAP: 3-aminophenol; meta-aminophenol NCI-831: Photopolymerization initiator "ADEKA ARCLES" (registered trademark) NCI-831 NMP: N-methyl-2-pyrrolidone ODPA: 4,4'-oxydiphthalic anhydride PGME: Propylene glycol monomethyl ether PGMEA: Propylene glycol monomethyl ether acetate S0100CF: "Irgaphor" (registered trademark) Black S0100CF SiDA: 1,3-bis(3-aminopropyl)tetramethyldisiloxane TrisP-PA: 1,1-bis(4-hydroxyphenyl)-1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethane (manufactured by Honshu Chemical Industry Co., Ltd.). Metal adsorbents: Triphenylphosphine,polymer-boundonstyrene-divinylbenzenecopolymer (Strem Chemicals).

[0174] <Synthesis of polyimide (PI-1)> Under a dry nitrogen stream, 58.6 g (0.16 mol) of BAHF and 8.7 g (0.08 mol) of 3-aminophenol as a terminal blocking agent were dissolved in 300 g of N-methyl-2-pyrrolidone (NMP). 62.0 g (0.20 mol) of ODPA was added together with 100 g of NMP, and the mixture was stirred at 20°C for 1 hour, and then at 50°C for 4 hours. Then, 15 g of xylene was added, and the mixture was stirred at 150°C for 5 hours while azeotroping water with xylene. After the stirring was completed, the solution was poured into 5 L of water to collect a white precipitate. The precipitate was collected by filtration, washed three times with water, and then dried in a vacuum dryer at 80°C for 24 hours to obtain the target polyimide (PI-1).

[0175] <Synthesis of polyimide precursor (PIP-1)> Under a dry nitrogen stream, 31.02 g (0.10 mol; 100 mol% relative to the structural units derived from all carboxylic acids and their derivatives) of ODPA and 150 g of NMP were weighed and dissolved in a three-neck flask. A solution of 25.64 g (0.070 mol; 56.0 mol% relative to the structural units derived from all amines and their derivatives) of BAHF and 6.21 g (0.0050 mol; 4.0 mol% relative to the structural units derived from all amines and their derivatives) of SiDA was added to 50 g of NMP, stirred at 20 ° C for 1 hour, and then stirred at 50 ° C for 2 hours. Next, a solution of 5.46 g (0.050 mol; 40.0 mol% relative to the structural units derived from all amines and their derivatives) of MAP was added to 15 g of NMP as a terminal blocking agent, and stirred at 50 ° C for 2 hours. Then, a solution of 23.83 g (0.20 mol) of DFA dissolved in 15 g of NMP was added. After the addition, the mixture was stirred at 50°C for 3 hours. After the reaction was completed, the reaction solution was cooled to room temperature, then added to 3 L of water, and the precipitated solid was filtered. The solid obtained was washed three times with water and then dried in a vacuum dryer at 80°C for 24 hours to obtain a polyimide precursor (PIP-1).

[0176] <Synthesis of acrylic copolymer (AC-1)> 100g of isopropyl alcohol was charged into a 1,000cc four-neck flask, and this was kept at 80°C in an oil bath, sealed with nitrogen, and mixed with 30g of methyl methacrylate, 40g of styrene, 30g of methacrylic acid, and 2g of N,N-azobisisobutyronitrile while stirring, and this was dropped into the flask over 30 minutes. After the reaction was continued for 4 hours, 1g of hydroquinone monomethyl ether was added, and the temperature was returned to room temperature to complete the polymerization. After synthesizing a methyl methacrylate / methacrylic acid / styrene copolymer (weight ratio 30 / 40 / 30) in this way, 40 parts by weight of GMA was added to 100 parts by weight of the copolymer, and the copolymer was reprecipitated in purified water, filtered, and dried to obtain an acrylic copolymer (AC-1) with a weight average molecular weight (Mw) of 30,000 and an acid value of 110 (mgKOH / g).

[0177] <Synthesis of photosensitizer (B-1)> Under a dry nitrogen stream, 21.22 g (0.05 mol) of TrisP-PA (trade name, manufactured by Honshu Chemical Industry Co., Ltd.) and 36.27 g (0.135 mol) of 5-naphthoquinone diazide sulfonyl chloride were dissolved in 450 g of 1,4-dioxane and brought to room temperature. 15.18 g of triethylamine mixed with 50 g of 1,4-dioxane was added dropwise so that the temperature in the system did not exceed 35°C. After the addition, the mixture was stirred at 30°C for 2 hours. The triethylamine salt was filtered, and the filtrate was poured into water. The precipitate was then collected by filtration. The precipitate was dried in a vacuum dryer to obtain a photosensitizer (B-1) which is a quinone diazide compound represented by the following formula.

[0178] [ka]

[0179] <Preparation of Photosensitive Resin Composition R-1> Under yellow light, (A) PI-1 (10.0 g) as an alkali-soluble resin, (B) B-1 (1.2 g) as a photosensitizer, and (C) PGME (32.0 g) and GBL (8.0 g) as organic solvents were added. The resulting solution was then filtered through a 0.45 μmφ filter to obtain a positive-type photosensitive resin composition R-1.

[0180] <Preparation of Photosensitive Resin Composition R-4> Under yellow light, (A) PIP-1 (10.0 g) as an alkali-soluble resin, (B) B-1 (1.2 g) as a photosensitizer, and (C) PGME (32.0 g) and GBL (8.0 g) as organic solvents were added. The resulting solution was then filtered through a 0.45 μmφ filter to obtain a positive-type photosensitive resin composition R-4.

[0181] <Synthesis of pigment dispersant> A pigment dispersant with an amine value of 20 (mgKOH / g) was synthesized as follows.

[0182] 103.00 g of diethylenetriamine (1 mol) was charged into pressure vessel 1, and the temperature was raised to 100° C. under a nitrogen atmosphere while stirring. Next, 4405.00 g of ethylene oxide (100 mol) was charged into pressure vessel 2, and the temperature was raised to 100° C. The vaporized ethylene oxide was pressurized with nitrogen gas and continuously fed into pressure vessel 1 through a gas inlet tube under a pressure of 0.1 to 0.3 MPa while stirring for 10 minutes, to obtain an addition reaction product A of diethylenetriamine and ethylene oxide.

[0183] The pressure vessel 1 was once naturally cooled to 25°C, and then opened. 0.5 g of potassium hydroxide was added as an alkaline catalyst to promote addition polymerization. After stirring, the temperature was raised again to 100°C. Vaporized ethylene oxide was continuously fed into the pressure vessel 1 while stirring for 2 hours, and addition reaction product B was obtained. Next, 5,810.00 g of propylene oxide (100 mol) was separately charged into the pressure vessel 3. The pressure vessel 3 was heated to 100° C., and the vaporized propylene oxide was continuously fed into the pressure vessel 1 through the gas inlet tube under a pressure of 0.1 to 0.3 MPa while being pressurized with nitrogen gas, and stirred for 3 hours to obtain an addition reaction product C.

[0184] The pressure vessel 1 was heated to 50°C, 50.00 g of a solid acid adsorbent (synthetic aluminum silicate) was added, and the mixture was stirred for 3 hours to adsorb the alkaline catalyst. The alkaline catalyst was then removed by filtration at room temperature / atmospheric pressure to obtain a pale yellow liquid pigment dispersant.

[0185] The end points of the amounts of ethylene oxide and propylene oxide fed into the pressure vessel 1 were set so that the average number of moles of ethylene oxide grafted onto diethylenetriamine was equal to the average number of moles of propylene oxide added, and the sum of the average number of moles added was set so that the amine value of the final pigment dispersant would be 20 (mgKOH / g).

[0186] <Preparation of pigment dispersion 1) 600g of S0100CF as a colorant, 468.5g of 20wt% PGMEA solution of acrylic copolymer (AC-1) as an alkali-soluble resin, 56.3g of the pigment dispersant with an amine value of 20 (mgKOH / g) and 1,875.2g of PGMEA as a polymer dispersant were charged in a tank and stirred for 20 minutes with a homomixer to obtain a preliminary dispersion. The preliminary dispersion was fed to a dispersing machine Ultra Apex Mill manufactured by Hiroshima Metal & Machinery Co., Ltd., equipped with a centrifugal separator filled with 70% by volume of 0.10mmφ zirconia beads, and dispersion was performed for 3 hours at a rotation speed of 10m / s to obtain a pigment dispersion 1 with a solid concentration of 25wt% and a colorant / resin (weight) = 80 / 20.

[0187] <Synthesis of radical polymerizable compound FA-1) In a 1L separable flask, 45g of 9-fluorenone (0.25 mol, manufactured by Osaka Gas Chemicals Co., Ltd.), 138g (1 mol) of ethylene glycol mono(2-naphthyl)ether, and 1g of 3-mercaptopropionic acid were added, and then heated to 60°C to completely dissolve. Then, 54g of sulfuric acid was gradually added, and the mixture was stirred for 5 hours while maintaining the temperature at 60°C. When confirmed by HPLC, it was confirmed that the conversion rate of 9-fluorenone was 99% or more. After neutralizing the obtained reaction liquid by adding 48% caustic soda water, 400g of xylene was added, washed several times with distilled water, and cooled to precipitate crystals. The obtained crystals were filtered and dried to obtain the desired 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene. When the HPLC purity of the obtained crystals was measured, 87g of the desired product with a purity of 98.3% was obtained (yield 67%). In addition, the obtained samples 1 The H-NMR and mass spectrometry confirmed that the product was the desired 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene. The ethylene glycol mono(2-naphthyl) ether used was purified (purity 99% or higher) from the reaction mixture obtained by reacting 2-naphthol with ethylene carbonate.

[0188] 43.8g (0.1 mol) of 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene thus obtained, 18.7g (2.6 mol) of acrylic acid, 2.2g of p-toluenesulfonic acid, 98g of toluene, and 0.21g of methoquinone were charged, and the dehydration esterification reaction was carried out while refluxing at 110°C to 115°C until the theoretical dehydration amount was obtained. Thereafter, the reaction liquid was neutralized with alkali and washed with 20% saline. After washing, the toluene was removed. In this way, compound FA-1 was obtained.

[0189] <Preparation of Photosensitive Resin Composition R-2> To 250.0 g of the pigment dispersion 1, (A) 386.5 g of a 20 wt % PGMEA solution of acrylic copolymer (AC-1) as an alkali-soluble resin, (B) 13.3 g of NCI-831 as a photopolymerization initiator, 4.7 g of FA-1 and 42.0 g of DPCA-60 as radical polymerizable compounds, 0.2 g of BYK-333 as a silicone surfactant, and (C) 490.8 g of PGMEA as an organic solvent were added to obtain a black negative photosensitive resin composition R-2 having a total solid concentration of 20 wt % and a color pigment / resin (weight ratio) of 25 / 75.

[0190] <Preparation of Photosensitive Resin Composition R-3> A negative photosensitive resin composition R-3 was obtained in the same manner as in the preparation of R-2, except that the pigment dispersion liquid 1 was not used.

[0191] <Preparation of pigment dispersion 2> 200 g of zirconium nitride particles (ZrN, manufactured by Nisshin Engineering Co., Ltd.) produced by a thermal plasma method, 50 g of polyimide precursor (PIP-1), and GBL (1000 g) were charged into a tank and stirred with a homomixer for 20 minutes to obtain a preliminary dispersion. The preliminary dispersion obtained was fed into a dispersing machine (Ultra Apex Mill, manufactured by Hiroshima Metal & Machinery Co., Ltd.) equipped with a centrifugal separator filled with 75% by volume of 0.05 mmφ zirconia beads, and dispersion was performed for 3 hours at a rotation speed of 10 m / s to obtain pigment dispersion 2 with a solid concentration of 20% by weight and a colorant / resin (weight ratio) of 80 / 20.

[0192] <Preparation of Photosensitive Resin Composition R-5> To 93.8 g of the pigment dispersion 2, (A) 50.5 g of PIP-1 as an alkali-soluble resin, (B) 17.0 g of B-1 as a photosensitizer, 13.6 g of a phenol compound (bisphenol AF (Tokyo Chemical Industry Co., Ltd.)), 0.2 g of BYK-333 as a silicone surfactant, and (C) 720.0 g of PGME and 105.0 g of GBL as organic solvents were added to obtain a black positive photosensitive resin composition R-5 having a total solids concentration of 10% by weight and a pigment / resin (weight ratio) of 15 / 85.

[0193] <Preparation of Coating Solution for Hole Injection Layer HT-1> The arylamine polymer shown in structural formula (HIT-1), 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate shown in structural formula (A-1), low molecular weight crosslinker 1, and ethyl benzoate as a solvent were mixed to obtain a coating solution for HT-1. The concentrations were HIT-1: 2.5% by weight, A-1: ​​0.5% by weight, and low molecular weight crosslinker 1: 0.25% by weight. p-Styryltrimethylsilane (KBM-1403, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the low molecular weight crosslinker 1. The solubility of this crosslinker in water was 1% or less.

[0194] [ka]

[0195] Low molecular weight crosslinker 1 is the compound shown below.

[0196] [ka]

[0197] <Preparation of Coating Solution for Hole Injection Layer HT-2> (Preparation of Pd catalyst) In a glove box under a nitrogen atmosphere, tris(dibenzylideneacetone)dipalladium (73.2 mg, 80 μmol) was weighed into a sample tube at room temperature, anisole (15 ml) was added, and the mixture was stirred for 30 minutes. Similarly, tris(t-butyl)phosphine (129.6 mg, 640 μmol) was weighed into a sample tube, anisole (5 mL) was added, and the mixture was stirred for 5 minutes. These solutions were mixed and stirred at room temperature for 30 minutes to obtain a Pd catalyst solution. In addition, in the preparation of the Pd catalyst, all solvents were degassed with nitrogen bubbles for 30 minutes or more before use.

[0198] (Preparation of polymer compound 1) A hole-transporting polymer compound 1 was prepared as follows. Polymer compound 1 is a compound having three or more branches and containing a structural unit derived from a condensed polycyclic aromatic hydrocarbon. In a three-necked round-bottom flask, the following monomer 1 (5.0 mmol), monomer 2 (3.5 mmol), monomer 3 (1.5 mmol), and anisole (20 ml) were added, and the Pd catalyst solution (7.5 ml) was further added and stirred. After stirring for 30 minutes, a 10% tetraethylammonium hydroxide aqueous solution (20 mL) was added to the flask. This mixture was heated and refluxed for 2 hours. All operations up to this point were performed under a nitrogen stream. All solvents were degassed by nitrogen bubbling for 30 minutes or more before use.

[0199] [ka]

[0200] After the reaction was completed, the organic layer was washed with water. The organic layer was then poured into methanol-water (9:1). The resulting precipitate was filtered by suction and washed with methanol-water (9:1). The washed precipitate was dissolved in toluene and poured into methanol for reprecipitation. The resulting precipitate was filtered by suction, dissolved in toluene, and a metal adsorbent (200 mg per 100 mg of polymer) was added and stirred overnight. After stirring was completed, the metal adsorbent and insoluble matter were removed by filtration, and the filtrate was concentrated with a rotary evaporator. The concentrated liquid was dissolved in toluene and poured into methanol-acetone (8:3) for reprecipitation. The resulting precipitate was filtered by suction and washed with methanol-acetone (8:3).

[0201] The number average molecular weight of the obtained polymer compound 1 was 3,300 and the weight average molecular weight was 30,600. In the polymer compound 1, the ratio of each structural unit derived from each monomer was monomer 5:15 mol %, monomer 2:50 mol %, and monomer 4:35 mol %.

[0202] (Preparation of Coating Solution) A coating solution for HT-2 was prepared, which consisted of polymer compound 1 (20 mg), ionic compound (I) shown below (1.0 mg), and toluene (2.3 mL).

[0203] [ka]

[0204] <Examples 1 to 12 and Comparative Examples 1 to 3> In each of the examples and comparative examples, the following organic EL display devices were fabricated, and the spacer structure was observed, a light emission color mixing test was performed, and a bending reliability test was performed.

[0205] First, amorphous ITO (10 nm), AgPdCu alloy (100 nm), and amorphous ITO (10 nm) were deposited in that order by vacuum sputtering in the center of a 100 mm x 100 mm PET substrate as the first electrode, and then 100 striped first electrodes with a line width of 60 μm, a pitch of 100 μm, and a length of 10 mm were formed by etching. In other words, the exposed part of the substrate was in the form of stripes with a width of 40 μm.

[0206] Furthermore, a photosensitive resin composition for forming a pixel dividing layer according to each of the examples and comparative examples shown in Table 1 was applied by spin coating, and then pre-baked on a hot plate at 100°C for 2 minutes to form a film.

[0207] This film was exposed to UV light through a stripe-patterned photomask, and then developed with a 2.38% TMAH aqueous solution to dissolve only the exposed areas. It was then rinsed with pure water to obtain a stripe-shaped pattern. The pattern was created by aligning the center lines with the gaps in the stripe-shaped first electrode, with a line width of 60 μm, a pitch of 100 μm, and a length of 10 mm, forming 101 stripes. It was then cured in an oven at 250° C. in a nitrogen atmosphere for 60 minutes to obtain a patterned substrate including a pixel division layer.

[0208] Furthermore, an excavation process was performed according to the center line of the pixel division layer with a line width of 60 μm, forming a concave structure with a width of 18 μm and a depth of T2 (μm) shown in Table 1 on the center line of the pixel division layer. Specifically, the area other than the area to be excavated was covered with ZEP520 (Zeon Corporation), a general-purpose photosensitive resist material, and processing was performed using an ICP-RIE device RIE-101iPHS-L (Samco Corporation), which enables anisotropic dry etching. Ar and O were used as the etching gas. 2 The desired concave structure was obtained by adjusting the gas mixture ratio and pressure, as well as the power output and temperature.

[0209] Thereafter, a photosensitive resin composition for spacer formation according to each of the examples and comparative examples shown in Table 1 was applied by spin coating, and then prebaked on a hot plate at 100 ° C for 2 minutes to form a film. This film was exposed to UV light through a photomask with a stripe pattern, and then developed with a 2.38% TMAH aqueous solution. In the case of a negative photosensitive resin composition, only the unexposed parts were dissolved, and in the case of a positive photosensitive resin composition, only the exposed parts were dissolved. Then, it was rinsed with pure water to obtain a spacer pattern having a stripe shape and the structure described in Table 1. The spacer pattern was prepared in a stripe shape with a line width of 20 μm, a pitch of 100 μm, and a length of 10 mm, aligned with the center line of the striped pixel division layer. Then, it was cured in an oven at 250 ° C in a nitrogen atmosphere for 60 minutes to obtain a patterned substrate having a structure in which the spacers are embedded in the pixel division layer. In Comparative Example 3, the spacers were not processed or prepared, and a substrate without spacers was used.

[0210] In this way, a striped substrate was obtained in which a pixel opening portion of 40 μm, a pixel division portion of 20 μm, a spacer portion of 20 μm, and a pixel division portion of 20 μm were repeated 100 times.

[0211] In preparation for forming the organic EL layer, the substrate was ultrasonically cleaned for 15 minutes using "Semicoclean" (registered trademark) 56 (manufactured by Furuuchi Chemical Co., Ltd.), and then washed with ultrapure water. Furthermore, immediately before forming the organic EL layer, the substrate was subjected to UV-ozone treatment for 1 hour.

[0212] Next, an organic EL layer consisting of a hole injection layer, a hole transport layer, a light emitting layer, and an electron transport layer was formed on the entire surface of the patterned substrate by coating or vacuum deposition. The hole injection layer and the electron transport layer are shown in Table 1.

[0213] The hole injection layer HT-1 was formed by forming a film of the HT-1 coating solution prepared as above on a substrate by spin coating under the following conditions to form a hole injection layer with a thickness of 30 nm. ·HT-1 deposition conditions (Spinner rotation time) 3000 rpm, 30 seconds (Heating conditions) Hot plate, 230℃, 20 minutes The hole injection layer HT-2 was formed by forming a film of the HT-2 coating solution prepared as above on a substrate by spin coating under the following conditions to form a hole injection layer with a thickness of 40 nm. ·HT-2 deposition conditions (Spinner rotation time) 3000 rpm, 30 seconds (Heating conditions) Hot plate, 180℃, 10 minutes The hole injection layer HT-3 was formed by vacuum deposition to a thickness of 10 nm. The degree of vacuum during deposition was 1×10 -3 The pressure was set to 0.1 Pa or less, and the substrate was rotated relative to the deposition source during deposition.

[0214] Next, HT-4 was evaporated to a thickness of 50 nm as a hole transport layer. Next, a mixed layer of host material H-1 and dopant material D-1 was evaporated to a thickness of 20 nm as a light emitting layer so that the doping concentration was 5% by weight. Next, an electron transport layer was evaporated to a thickness of 20 nm. Table 1 shows the combination of the hole injection layer and the electron transport layer in each example and comparative example.

[0215] HT-3, HT-4, H-1, and D-1 are the compounds shown below.

[0216] [ka]

[0217] Furthermore, ET-1, ET-2, and ET-3 are the compounds shown below.

[0218] [ka]

[0219] After that, 20 stripe-shaped second electrodes were formed by vapor deposition of 10 nm of Mg and Ag at a volume ratio of 10:1, with a line width of 400 μm, a pitch of 500 μm, and a length of 10 mm, so as to intersect with the first electrodes. Note that the film thickness referred to here is the value displayed on a quartz crystal oscillation film thickness monitor.

[0220] In this way, an organic EL display device having 100 first electrodes, 20 second electrodes, and 200 light-emitting elements in which the first electrodes and the second electrodes intersect was completed. A schematic diagram of an organic EL display device 13 of this example is shown in FIG.

[0221] Table 1 shows the results of evaluation of the organic EL display devices of the examples and comparative examples, including spacer structure observation, a light emission color mixing test, and a bending reliability test.

[0222] [Table 1] [Industrial Applicability]

[0223] The organic EL display device of the present invention can be used as an organic EL display device with high bending reliability. [Explanation of symbols]

[0224] 1 Base material 1a Base of the substrate 2 First electrode 3. Pixel division layer 4 Spacer 5 Organic EL layer 6 Second electrode 7. TFT 8 Planarization layer 9 Sealing layer 10 Polarizing layer 11 UV absorbing layer 12 Cylinder 13 Organic EL display device

Claims

1. An organic EL display device having a substrate, an organic EL layer, and a second electrode, the substrate having a first electrode, a pixel division layer, and a spacer having an inverted tapered shape on a base material, and a portion of the spacer having an inverted tapered shape is embedded in the pixel division layer.

2. 2. The organic electroluminescence display device according to claim 1, wherein when a film thickness of the inverted tapered spacer is T1 (μm), a depth to which a portion of the inverted tapered spacer is embedded in the pixel division layer is T2 (μm), and a film thickness of the pixel division layer is T3 (μm), T1, T2, and T3 satisfy the following condition 1: Condition 1: T3≧T2≧T1×0.2

3. 3. The organic electroluminescence display device according to claim 2, wherein T1, T2 and T3 satisfy the following condition 2: Condition 2: T3 = T2 ≧ T1 × 0.2

4. The organic electroluminescence display device according to claim 1 , wherein the spacer having an inverse tapered shape contains a coloring material.

5. The organic electroluminescence display device according to claim 1 , wherein the organic electroluminescence layer contains a hole-transporting polymer compound.

6. The organic electroluminescence display device according to claim 1 , wherein the organic electroluminescence layer contains a compound having a phenanthroline skeleton.

7. The organic electroluminescence display device according to claim 1 , wherein the organic electroluminescence layer contains a compound having a terpyridine skeleton.

Citation Information

Patent Citations

  • Light emitting device and electronic device

    JP2012074238A

  • Photosensitive resin composition, method of producing cured film, cured film, liquid crystal display device and organic el display device

    WO2015046296A1